Insights into physicochemical, techno-functional, crystalline and thermal properties of arrowroot (Maranta arundinacea L.) starch modified by plasma activated water - Himashri Konch; Rakesh Kumar Gupta; Prem Prakash Srivastav (Food and Humanity, 2026)

Spatiotemporal variations and environmental correlates of Apocyclops and Dioithona (Cyclopoida: Copepoda) in tropical coastal waters: Implications for optimizing hatchery feed - Duraivel Prem Kumar; Philip Theodore Reginald; Arasarathinam Dennis; Kareem Altaff; Barathan Balaji Prasath; Deepali Desai; Radha Vijayaraj (Continental Shelf Research, 2026)

CRESS domain-based molecular characterization of Begomovirus gossypimultanense - Niranjana Prem Minipreman; Marimuthu Elangovan; Nikeshun Vivekananthan; Archana Rathore; Susheel kumar; Ashok Kumar; Kajal Kumar Biswas; Vijayanandraj Selvaraj (Molecular Biology Reports, 2026)

Comparative performance of traditional and commercial DNA extraction methods for fish gut microbiota analysis - Amrita Mohanty; Annam Pavan-Kumar; Aparna Chaudhari; Kavita Kumari; Prem Kumar; Praveen Maurye (Molecular Biology Reports, 2026)

Pharmacological inhibition of IRAK1/4 ameliorates high-fat diet-induced vascular dysfunction and cognitive impairment - Dinesh Kumar; Sakesh Kumar; Heena Agarwal; Gagandeep Kaur; Prem N. Yadav; Manoj Kumar Barthwal (Molecular Biology Reports, 2026)

3D printed smartphone device with nano-upconversion cellulose paper for soil boron assessment - Kamaljit Kaur; Abhijith TS; Sudarshan Sahu; Shailendra Kumar Arya; Neeraj Moun; Prem Kumar; Priya Padmanabhan; Nishima Wangoo; VijayaKumar Shanmugham (Analytica Chimica Acta, 2026)

Plant proteins for functional food gels: sources, extraction technologies, sustainable gelation approaches, and applications in food systems - U. Gnana Moorthy Eswaran; Rakesh Kumar Gupta; Rubeka Idrishi; Madhumitha Muthrajan; Devanampriyan Rajan; Sairagul Giridharaprasad; Sitesh Kumar; Sunil Pipliya; Santhosh Ravichandran; Prem Prakash Srivastav (Food Research International, 2026)

Pentavalent molybdenum species supported on coal waste derived ZSM-5 enhances the activity and stability of the catalyst for methane dehydroaromatization (MDA) reaction - Anil Chandra Kothari; Akashdeep Karmakar; Punit Kumar; Rubina Khatun; Sonu Bhandari; Rohan Singh Pal; Kapil Bhati; Shivani Singh; Takehiko Sasaki; Tuhin Suvra Khan; Prem Lama; Rajaram Bal (Chemical Engineering Journal, 2026)

A lithium isotopic perspective of basalt weathering: Cycling of Li and its mobility relative to Ca and Mg - Anup Kumar Sharma; Tarun Kumar Dalai; Sambuddha Misra; Prem Chand Kisku; Jitendra Kumar Pattanaik (Chemical Geology, 2026)

Identifying the Thermal Stress and Bleaching Risks associated with Sea Surface Temperature Variability and El-Nino on Coral Reefs Surrounding the Andaman and Nicobar Groups of Islands - Jaya Rai; Prem Kumar; Benidhar Deshmukh; Pramod Kumar; Anant Dikshit (Regional Studies in Marine Science, 2026)

Spatiotemporally controlled peroxynitrite nanogenerator disarms tumor physical barriers to potentiate immune activation - Qize Xuan; Jiazhe Cai; Qian Hu; Xinchi Qiao; Yuan Gao; Yifan Feng; Xinyu Yu; Dawei Jiang; Damià Barceló; Alan Prem Kumar; Chao Chen; Hui Li (Chemical Engineering Journal, 2026)

Towards climate-resilient rice (Oryza sativa L.): re-engineering root system architecture for abiotic stress tolerance: a review - Prem kumar Ajmeera; Manonmani Swaminathan; Gopalakrishnan Chellappan; Sritharan Natarajan; Rajeswari Sivakami (Euphytica, 2026)

Genetic architecture of Karnal bunt resistance in wheat: A review - Rajesh Aggarwal; Satish Kumar; Vikram Singh; Prem Lal Kashyap; Chandra Nath Mishra; Rajender Singh; Ratan Tiwari (Cereal Research Communications, 2026)

Resveratrol and neuroprotection: modulation of cellular dynamics and signaling networks in neurodegenerative diseases - Md Abul Hassan; Md. Al Amin; Sherouk Hussein Sweilam; Mohammad Abohassan; Karthickeyan Krishnan; Jeetendra Kumar Gupta; Patibandla Jahnavi; Rajeshwar Vodeti; R. Radha; Prem Shankar Gupta; Konatham Teja Kumar Reddy (Inflammopharmacology, 2026)

Suitability analysis of agroforestry in Himachal Pradesh by using a multi-criteria GIS–AHP approach - Saakshi; D. R. Bhardwaj; Prem Prakash Sharma; Dushyant Sharma; Rahul Bodh; Avinash Kumar Bhatia (Agroforestry Systems, 2026)

Automatic classification of avalanche and non-avalanche events in seismic data using machine learning - Hemant; Mukesh Kumar; Neelam Goel; P K Srivastava; Prem Datt (Journal of Earth System Science, 2026)

Powdery Mildew (Blumeria hordei) Resilience in Barley: From Physiological to CRISPR-Driven Resistance - Madhu Patial; Santosh Kumar Bishnoi; Prem Lal Kashyap; Vandana Thakur; Dharam Pal; Kallol Kumar Pramanick; Ruchi Bansal (Physiological and Molecular Plant Pathology, 2026)

Precision veterinary therapeutics through nanomedicine: Platforms, applications, and One Health implications - Amit Kumar Verma; Arbind Singh; Ajit Kumar Singh; Prem Sagar Maurya; Vikas Jaiswal; Vikas Sachan (Next Research, 2026)

In vivo anthelmintic efficacy, hematobiochemical and antioxidant effects of Swertia chirata in Barbari goats naturally infected with Haemonchus contortus - Ramakant; Tarun Kumar Sarkar; Prem Sagar Maurya; Arbind Singh; Vikas Jaiswal; Ayush Pal; Devesh Kumar Yadav; Amit Kumar Verma (Tropical Animal Health and Production, 2026)

Impact of lycopene supplementation on oxidative balance, heat-shock proteins, and lipid profile in heat-stressed goat kids - Atul Kumar Verma; Gulab Chandra; Rakesh Kumar Singh; Devesh Kumar Yadav; Prem Sagar Maurya; Ahmad Fahim; Debashis Roy; Pratibha Singh; Priyanka Rani; Mala Singh (International Journal of Biometeorology, 2026)

Assessing Mining-Induced Groundwater Level Decline Using Integrated Spatial and Statistical Techniques in the Moher Sub-basin, Singrauli Coalfield, India - Rahul Karki; Abul Amir Khan; S. K. Gara; Prem Kumar; Sahil Wadhwa (Mine Water and the Environment, 2026)

Crossroad Between Gut Microbiome and Ischemic Stroke: Underlying Pathways and Therapeutic Possibilities - Shivashish Dobhal; Meenakshi Kaushik; Prem Lata Manhas; Ankur Kumar; Priyanka Naithani; Prakamya Gupta; Hitaishi Kaushik; Manisha Naithani; Balram Ji Omar; Ashish Kothari; Akshat Uniyal; Yogendra Pratap Mathuria; et al. (Indian Journal of Microbiology, 2026)

Mathematical modeling and transmission insights into Mpox: dynamics, control measures, and data-driven validation - G. Swathi; G. S. Mahapatra; R. Prem Kumar (Theory in Biosciences, 2026)

Synthesis of silver nanoparticles from Azadirachta indica and Justicia adhatoda leaves and assessment of their antibacterial properties - Gunanand Pant; Prem Singh Saud; Prem Raj Joshi; Tek Raj Ojha; Indra Ojha; Sanjay Kumar Garg; Alok Srivastava; Pankaj Kumar Arora; Vijay Kumar Sinhal (Next Research, 2026)

Nanotechnology-enabled sustainable food packaging systems: A comprehensive review on materials, mechanisms, and applications in food quality and safety - Rakesh Kumar Gupta; N.Sai Prasanna; Jyotsana Patel; Sunil Pipliya; Selvakumar Murugesan; Sitesh Kumar; Prem Prakash Srivastav (Food and Humanity, 2026)

The effect of silymarin and nano zinc supplementation on growth, immunity, antioxidant, and metabolic hormone status of Murrah buffalo calves - Deepak Singh; Dev Saran Sahu; Gulab Chandra; Satya Prakash Yadav; Debashis Roy; Rakesh Kumar Singh; Devesh Kumar Yadav; Ahmad Fahim; Prem Sagar Maurya; Pankaj Kumar Maurya; Karunesh Kumar Dubey (Animal Feed Science and Technology, 2026)

Symbiont dominance and microbiome dysbiosis in wheat-aphid revealed through 16 S rRNA gene amplicon sequencing analysis - Poonam Jasrotia; Priyanka Chandra; Arjun Singh; Prem Lal Kashyap; Susheel Kumar Sharma (World Journal of Microbiology and Biotechnology, 2026)

Genome wide comparative analysis of microsatellites in Bipolaris sorokiniana for diversity analysis and spot blotch disease diagnosis in wheat - Prem Lal Kashyap; Sudheer Kumar; Annie Khanna; Anju Sharma; Sunita Mahapatra; Pradeep Sharma; Ratan Tiwari (World Journal of Microbiology and Biotechnology, 2026)

Evaluation of MERRA-2 PM2.5 species at three locations in India and their historical (1999–2019) trends - Sandeep Devaliya; Sayak Patra; Prem Maheshwarkar; Ankur Bhardwaj; Diksha Haswani; Deeksha Shukla; Ramya Sunder Raman; Abisheg Dhandapani; R. Naresh Kumar; Jithin K. P.; Lokesh Kaggere (Environmental Monitoring and Assessment, 2026)

Standardization and bioactivity validation of Palasabijadi Churna: A classical ayurvedic remedy for infections and inflammation - Kousik Ghosh; K. Vamsee Krishna; Lakshmanan Narayanan; Prem Kumar; Chidanandamurthy Thippeswamy Swamy; M.C. Soumya; Vinodkumar Thallada; S. Chitra; Preeti Sharma; Ajay Kumar Meena (Next Research, 2026)

Systematic investigation of aflatoxigenic Aspergillus flavus inhibition: Integrating essential oils-based formulation with mathematical modeling and transcriptomic analysis - Prem Pratap Singh; Ritu Singh; Praveen Kumar Verma; Bhanu Prakash (International Journal of Food Microbiology, 2026)

Climate-resilient agriculture strategies to address the challenges of agri-food security and climate change - Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Shubham Durgude; Suneel Kumar; Illathur R. Reddy; S. Pazhanisamy; et al. (Field Crops Research, 2026)

Box-Behnken Design Optimization of pH-Responsive Chitosan-Graphene Oxide Nanocomposite Hydrogel for Sustained Levofloxacin Delivery in Antimicrobial Wound Therapeutics - Priyanka Rathore; Prem Prakash Singh; Peeyush Bhardwaj; Anshu Awasthi; Brajesh Lodhi; Prakash Chandra Yadav; Ankita Kishore; Prashant Pandey; Alok Kumar Mahor (Journal of Pharmaceutical Innovation, 2026)

Comparative efficacy of transdermal buprenorphine versus diclofenac in the management of knee osteoarthritis: a randomized controlled trial with network pharmacology insights - Abhay Singh; Sneha Yadav; Anil Kumar Gulia; Shivani Singh; Sanjeev Bansal; Prem Shankar Gupta; Soniya Rani (Inflammopharmacology, 2026)

Ecological interactions among plants, honeybees, and microbes: implications for sustainable ecosystems - Prem Siva Naga Teja Alapati; Dharmender Kumar; Baljeet Singh Saharan (Journal of Asia-Pacific Entomology, 2026)

Comparative evaluation of oxytetracycline and an herbal formulation in the treatment of bovine anaplasmosis - Aditya Kumar; Arbind Singh; Amit Kumar Verma; Anu Rahal; Amit Kumar; Prem Sagar Maurya (Tropical Animal Health and Production, 2026)

Captive Breeding, Embryonic Development, and Larval Weaning of Lesser Spiny Eel, Macrognathus Aculeatus (Bloch, 1786) - Bhumika Gamango; Pravesh Kumar; Shivendra Kumar; Roshan Kumar Ram; Prem Prakash Srivastava; H. S. Mogalekar; Raj Kamal Mishra; Aditi Banik (Thalassas: An International Journal of Marine Sciences, 2026)

A comprehensive review on algal bioactive compounds with emphasize on its allergenicity reduction, health benefits and applications in food industry - Soubhagya Tripathy; Srutee Rout; Rahel Suchintita Das; Brijesh Kumar Tiwari; Marco Garcia-Vaquero; Prem Prakash Srivastav (Food Bioscience, 2026)

Glycocin-incorporated cellulose nanofiber: An antibacterial polymeric film for food packaging and preservation - Shimona Ahlawat; Prem Kumar; Kulwinder Singh Sran; Ved Prakash Giri; Kamaljit Kaur; Vijayakumar Shanmugam; Alka Rao (Chemical Engineering Journal, 2026)

Integrated computational-experimental pipeline for CHK1 inhibitor discovery: structure-based identification of novel chemotypes with anticancer activity - Dhanushya Gopal; Manasa Pacharla; Nehal Arvind Kumar; Prem Kumar; Angelin Preetha Sathiyanathan; Jaikanth Chandrasekaran; Mohit Agrawal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Dietary Saraca asoca bark powder as a reproductive enhancer: Insights into endocrine, molecular, oxidative, and reproductive tissue biomarkers in female climbing perch (Anabas testudineus) - Maneesh Kumar Dubey; Shivendra Kumar; Prem Prakash Srivastava; Aditi Banik; R.K. Brahmchari; Pankaj Kishore; Amit Kumar; Rini Joshi (Animal Feed Science and Technology, 2026)

Unveiling the multitarget anticancer potential of Cochlospermum religiosum: phytochemical profiling, molecular docking, and in vitro/in vivo validation - SaiPrasanna Rasamalla; Jayhind Bharti; Priyadharshini Gogu; Maria Grishina; Sarvesh Kumar Pandey; Prem Shankar Gupta; Dileep Kumar; Ashish Ranjan Dwivedi; Prateek Pathak (DARU Journal of Pharmaceutical Sciences, 2026)

Synthesis, Characterization, Photoluminescence Properties of Rare-Earth Free Activated Sr2GeO4 for Lighting Applications - Salivoju Venkateshwarlu; Putta Shekar; Ramatenki Prem Kumar; Muga Vithal; Mudavat Srinivas (Journal of Fluorescence, 2026)

Climate-resilient agri-food systems: analyzing yield trends and overcoming adoption barriers - Shubham Durgude; Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Dinesh Chand Meena; Suneel Kumar; Illathur R. Reddy; et al. (Environment, Development and Sustainability, 2026)

Characterization and Evaluation of P Solubilizing Bacteria from Forest Soils for Plant Growth Promotion - Hillol Chakdar; Pragya Saxena; M. Kumar; Arjun Singh; Samadhan Y. Bagul; Shaloo Verma; Sudipta Das; Prem Lal Kashyap; Anil Kumar Saxena (Indian Journal of Microbiology, 2026)

Species richness, substrata preference, and phorophyte specificity of North-Western Indian Himalayan moss species - Anshul Dhyani; Siddhartha Kaushal; Kumar Shantanu; Sanavar Soham; Meenam Bhatia; Prem Lal Uniyal (Environmental Monitoring and Assessment, 2026)

From Molecular Networks to Medicines: Targeting Complexity in Alzheimer’s Disease (AD) Therapy - Rahul Kumar; Sakshi Patel; Prem Shankar Mishra; Shriyansh Srivastava; Sathvik Belagodu Sridhar; Javedh Shareef; Rakesh Sahu; Mohd Tariq; Jalal Uddin; Abdullatif Bin Muhsinah (Molecular Neurobiology, 2026)

Soil erosion: assessing riverbank erosion dynamics in Jorhat district of Assam, India using revised MMF model and GIS techniques - Bipasha Borkotoky; Bipul Deka; Prem Kumar Bharteey; Marami Dutta; Priyanuz Goswami; Mudassir Khan; Sanjay Kumar Chetia; Santosh Kumar Sah (Environmental Geochemistry and Health, 2026)

Traditional Grewia optiva based agroforestry systems in the northwestern himalayas: a comprehensive study of carbon, soil health, and nutritional value - Ashok Kumar; Rohit Bishist; D. R. Bhardwaj; Rajesh Kaushal; Prem Prakash; Rishav Sharma; Krishan Lal Gautam; Sakshi Tomar (Agroforestry Systems, 2026)

Baicalein isolated from Oroxylum indicum acts as a potent µ- and κ-opioid receptor antagonist agent via the reversal of agonist-mediated cAMP inhibition - Kishan Singh; Anubhav Yadav; Sana Khan; Arti Shukla; Maksood Alam; Ashutosh Kumar Verma; Neerja Tiwari; Feroz Khan; Prem Narayan Yadav; Kapil Dev (Natural Product Research, 2025)

Taxonomic significance of pollen micromorphology in family Malvaceae from subtropical ecosystems - Prem Kumar; Mushtaq Ahmad; Syed Waseem Gillani; Muhammad Manzoor; Shazia Sultana; Lixin Zhang; Sokhib Islamov; Jamil Raza (Genetic Resources and Crop Evolution, 2025)

Foxtail millet bran as a functional feed ingredient: Effects on growth, feed efficiency, and nutrient digestibility in grass carp (Ctenopharyngodon idella) - Aditi Banik; Shivendra Kumar; Maneesh Kumar Dubey; R.K. Brahmchari; Sujit Kumar Nayak; Prem Prakash Srivastava (Animal Feed Science and Technology, 2025)

Wild pomegranate based intercropping: assessing fertilization and varietal response on crop production and soil physico-chemical properties - Sheetal Thakur; Kashmir Singh Pant; Rohit Bishist; Prem Prakash; Harish Sharma; Avinash Kumar Bhatia; Shiva Janju; Sahil Chauhan (Agroforestry Systems, 2025)

Mapping agro-potential through evaluating soil suitability and crop productivity using geospatial techniques - Rituparna Saikia; Dilip Kumar Patgiri; Bipul Deka; Prem Kumar Bharteey; Suman Dutta; Ramani Kanta Thakuria; Marami Dutta; Sanjib Ranjan Borah; Rahul Sadhukhan; Ranabir Chakraborty; Malini Roy Choudhury; Parag Saikia; et al. (Environmental Monitoring and Assessment, 2025)

Molecular characterization and phylogenetic insights into Theileria annulata affecting cattle in Western Uttar Pradesh, India - Vishnu Kumar Rai; Arbind Singh; Amit Kumar Verma; Prem Sagar Maurya; Vikas Jaiswal; Ramakant; Surendra Upadhyay; Ayush Pal (Tropical Animal Health and Production, 2025)

Optimization of performance and emissions of a diesel engine using acetylene-enriched waste cooking biodiesel - Suraj Bhan; Prem Shanker Yadav; Girish Gautam; Ragvendra Gautam; Saket Kumar; Manish Kumar (Clean Technologies and Environmental Policy, 2025)

Evaluation of efficacy of vermicompost application to aquaculture wastewater and its impact on growth performance of Channa striata and Lactuca sativa L. in aquaponics - Venisza Cathy John; Ajit Kumar Verma; Murtaza Hasan; Hare Krishna; Prativa Sahu; Prem Kumar; Tincy Varghese; Chandrakant Mallikarjun Hittinahalli; Manjulesh Pai (Aquaculture International, 2025)

Depiction of new flavonoids from Nyctanthus arbor-tristis , their antimicrobial activity and drug-likeness prediction - Preeti Singh; Surabhi Yadav; Alok Kumar Mahor; Prem Prakash Singh; Kuldeep K. Bansal (Natural Product Research, 2025)

In situ evaluation of genotoxicity and cytotoxicity associated with microplastics in an intertidal clam, Gafrarium divaricatum (Gmelin, 1791) - M. Harshavarthini; Shubra Singh; Prem Kumar; Martin Xavier; Saurav Kumar; Nalini Poojary; Madhuri S. Pathak; Kiran D. Rasal; Gajanan S. Ghode; Naresh S. Nagpure (Marine Pollution Bulletin, 2025)

Ecofriendly agriculture pest control using pheromone packed programed nanovolcanoes framed by graphene oxide - Kamaljit Kaur; Mahima Chandel; Vinay Kumar Thirumalahatti Munikrishnappa; Prem Kumar; Bandana Kumari Sahu; Momin Ahamed; Sowmya Manjunath; Markandeya Gorantla; Shannon Olsson; Eswaramoorthy Muthusamy; Kesavan Subaharan; Vijayakumar Shanmugam (Clean Technologies and Environmental Policy, 2025)

Global Trends and Advances in Vermicomposting: a Bibliometric Analysis of its Multidisciplinary Applications - Ashutosh Kumar; Mukesh Pandey; Aparna Srivastava; Kanchan Pant; Aman Gupta; Prem Ranjan (Circular Economy and Sustainability, 2025)

Aquaponics performance optimization: The impact of hydraulic loading rate on striped murrel (Channa striata) and lettuce (Lactuca sativa L.) production in a vermicompost-supplemented system - Venisza Cathy John; Ajit Kumar Verma; Murtaza Hasan; Hare Krishna; Prativa Sahu; Kishore Kumar Krishnani; Sukham Munilkumar; Prem Kumar; Tincy Varghese; Chandrakant Mallikarjun Hittinahalli (Aquacultural Engineering, 2025)

Effect of organic mulches and farming practices on strawberry yield and economics under wild pomegranate-based agroforestry in the western Himalayas - Anshul Thakur; Prem Prakash; Rohit Bishist; Pramod Verma; D. R. Bhardwaj; Harish Sharma; Avinash Kumar Bhatia; Sheetal Thakur; Pooja (Agroforestry Systems, 2025)

Optimizing tree spacing and nutrient management for marigold cultivation under Mangifera indica-based agroforestry system in submontane low hill zone of the North-Western Himalaya - Sahil Chauhan; Vipan Guleria; Prem Prakash; Shreya Chauhan; Avinash Kumar Bhatia; Hitesh Gupta; Sandeep Kumar; Ankita Chauhan (Agroforestry Systems, 2025)

Geochemistry of the siliciclastic sediments from the Raniganj Gondwana basin, West Bengal, India, and its geological implications - Y. Priyananda Singh; Oinam Kingson; K. Milankumar Sharma; Raghavendra Prasad Tiwari; Rajeev Patnaik; Prosenjit Ghosh; Anupam Sharma; Jitendra Kumar Pattanaik; Pankaj Kumar; Harel Thomas; Ningthoujam Premjit Singh; Prem Chand Kisku; et al. (Acta Geochimica, 2025)

Assessment and prediction of forest structural attributes in tropical deciduous forests - Pavan Kumar; Prem Chandra Pandey; Azad Rasul; Ramesh K. Ningthoujam (International Journal of Remote Sensing, 2025)

Altitude-driven changes in carbon storage, soil properties, and leaf nutritional value of Quercus semecarpifolia in the northwestern Himalayas - Rishav Sharma; Rohit Bishist; Rajesh Kaushal; Prem Prakash; Krishan Lal Gautam; Ashok Kumar; Harish Sharma; Varun Thakur; Munesh Kumar (Environmental Sustainability, 2025)

Diversity and abundance of rice hopper complex under natural farming in Himachal Pradesh, India - Aarushi Sharma; Pawan Kumar Sharma; Prem Chand Sharma; Ajay Sood; Arun Kumar (International Journal of Tropical Insect Science, 2025)

Essential oil-embedded starch based films for active packaging: Insights into migration, stability, and preservation efficiency - Rakesh Kumar Gupta; Sunil Pipliya; Jyotsana Patel; Prem Prakash Srivastav; Roberto Castro-Muñoz; Chin-Kun Wang; Monica R. Nemţanu (Trends in Food Science & Technology, 2025)

Heat shock protein B1 and NADPH oxidase 4 expression is associated with vital signs and antioxidant parameters in two different varieties of turkey under thermal stress - Kulvir Pal Singh; B.V. Sunil Kumar; Prem Prakash Dubey; Nitin Mehta (Research in Veterinary Science, 2025)

Phenotyping and deciphering genetic resistance to yellow rust in wheat through marker-assisted analysis - Munish Leharwan; Ankit Kumar Singh; Ankush Kumar; Prem Lal Kashyap; Sudheer Kumar; Rajender Singh; Om Prakash Gangwar (Physiological and Molecular Plant Pathology, 2025)

Engineering single Pd atom in W18O49 nanowire for ultra-sensitive crop pest detection and remote data communication - Prem Kumar; Kanchan Swami; Nilakantha Tripathy; Rajashri R. Urkude; Ankita Dadhich; Parul Sharma; Manish Singh; Kesavan Subaharan; Abir De Sarkar; Vijayakumar Shanmugam (Chemical Engineering Journal, 2025)

Release and partitioning of neodymium and its radiogenic isotope during basaltic weathering - Anup Kumar Sharma; Tarun Kumar Dalai; Prem Chand Kisku; Jitendra Kumar Pattanaik; Sambuddha Misra; Shivansh Verma; Anil Dutt Shukla (Chemical Geology, 2025)

Epigenetic Alterations Induced by Air Pollution: A Key Driver in Atherosclerosis Development - Pouya Goleij; Mohammad Amin Khazeei Tabari; Pantea Majma Sanaye; Ali Moradi; Hossein Karimi; Aryan Rezaee; Alan Prem Kumar; Haroon Khan (Cardiovascular Toxicology, 2025)

Endocrine disruption of Triphenyl Phosphate via VIT-2 in Caenorhabditis elegans: A comparative analysis with estradiol and 4-hydroxytamoxifen - Chongli Shi; Mengyan Huang; Yang Zheng; Chen Wang; Hiu Yan Lam; Susu Wang; Lingjun Zeng; Yi Peng; Yulun Gu; Yu Li; Haibin Hao; Haibo Chen; et al. (Journal of Hazardous Materials, 2025)

Upconversion enabled innovation: Transfer of lab sensor to smartphone based field device - Kamaljit Kaur; Navjeet Kaur; Kanchan Swami; T.S. Abhijith; Neeraj Moun; Prem Kumar; Madhu Khatri; VijayaKumar Shanmugam (Food Research International, 2025)

GIS-Based Hydro-Geo-Chemical Study of the Groundwater and Its Multivariate Statistical Assessment for Drinking and Irrigation Suitability in Dumka Region, Jharkhand, India - Mansi Srivastava; Prem Kumar Srivastava (International Journal of Environmental Research, 2025)

Therapeutic potential of melatonin-induced mitophagy in the pathogenesis of Alzheimer’s disease - Pouya Goleij; Mohammad Amin Khazeei Tabari; Mohadeseh Poudineh; Pantea Majma Sanaye; Haroon Khan; Alan Prem Kumar; Danaé S Larsen; Maria Daglia (Inflammopharmacology, 2025)

Mechanical performance of fiber reinforced concrete incorporating rice husk ash and brick aggregate - Pramod Kumar; Rajnikant Upadhyay; Keshav Kumar Sharma; Seeram Madhuri; Abhilash Gogineni; Prem Kumar Vagestan (Innovative Infrastructure Solutions, 2025)

Optimizing growth and yield: Nutrient source effects on Brassica campestris var. brown sarson under high density Malus × domestica Borkh. based agri-horticultural system in the Western Himalayas - Babita Kumari; K. S. Pant; Rohit Bishist; Prem Prakash; Avinash Kumar Bhatia (Agroforestry Systems, 2025)

Trends and advances in liposome formulation technology with an emphasis on ensuring safety and quality in food and drug applications - Pawan Prabhakar; Soubhagya Tripathy; Deepak Kumar Verma; Smita Singh; Mamta Thakur; Amit Kumar Singh; Prem Prakash Srivastav; Mamoni Banerjee; Ami R. Patel; Mónica L. Chávez González; Gemilang Lara Utama; José Sandoval-Cortés; et al. (Food Bioscience, 2025)

Groundwater prospect and quality assessment in arid region, NW India: Implications from weighted overlay analysis and electrical resistivity tomography - Rishu Pandey; Dewashish Kumar; Prem Prakash Dookia (Journal of Earth System Science, 2025)

Alternative raw materials for methanol oxidative dehydrogenation catalysts - Tiina Laitinen; Mohammad I.M. Alzeer; Harisankar Sreenivasan; Jennyffer Martinez-Quimbayo; Prem Seelam Kumar; Riitta L. Keiski; Satu Ojala (Journal of Environmental Chemical Engineering, 2025)

A comprehensive analysis on cost, combustion, performance and emissions for diesel engine fueled with preheated esters of waste cooking oil - Prem Shanker Yadav; Saket Kumar; Raghvendra Gautam (Clean Technologies and Environmental Policy, 2025)

Impact of multipurpose farm trees in subtemperate agroecosystems: benefits for soil, biomass, fodder, and climate resilience - Rushal Dogra; Kashmir S. Pant; Rohit Bishist; Prem Prakash; Praveen Kumar (Agroforestry Systems, 2025)

Predatory Behavior of Wasp Species, Antagonistic Defense Mechanism of Apis mellifera Honey Bees and Effective Wasp Management in Apiaries - Mohammad Ilyas Motmayen; Surender Kumar Sharma; Prem Chand Sharma; Shivani (Agricultural Research, 2025)

Mimosa pudica linn seed derived natural piezoelectric nanogenerator and separator for RGO/NiZTO based high performance supercapacitor - Prem Pal Singh; Suman Kumar Si; Bhanu Bhusan Khatua (Chemical Engineering Journal, 2025)

From bench to bedside: exploring curcumin-driven signaling pathways in immune cells for cancer management - Pouya Goleij; Aryan Rezaee; Hiu Yan Lam; Mohammad Amin Khazeei Tabari; Noureldeen Ouf; Dorsa Alijanzadeh; Pantea Majma Sanaye; Danaé S. Larsen; Maria Daglia; Haroon Khan; Gautam Sethi; Alan Prem Kumar (Inflammopharmacology, 2025)

Evaluation of rice distillers' dried grains soluble (DDGS) blended with non-starch polysaccharidases (NSPase) as a fish meal substitute in the diet of climbing perch, Anabas testudineus juveniles - Joynal Abedin; Shivendra Kumar; Aditi Banik; R.K. Brahmchari; Pankaj Kishore; Maneesh Kumar Dubey; Rinki Kumari; Prem Prakash Srivastava (Animal Feed Science and Technology, 2025)

Eco-friendly Nano-copper Synthesis: Gene and Enzyme Modulation for Combating Cadmium and Ammonia Toxicity in Fish - Pranita Ganeshkar; Rajesh Sharma; Tarkeshwar Kumar; Prem Kumar; Kotha Sammi Reddy; Neeraj Kumar (Biological Trace Element Research, 2025)

QbD-Based Development of Fluocinolone Nanocomposite Transdermal Gel: Optimization, Characterization, and Enhanced Anti-hyperpigmentation Efficacy Assessment - Priyanka Rathore; Rishikesh Gupta; Prem Prakash Singh; Anshu Awasthi; Ankita Kishore; Kuldeep K. Bansal; Alok Kumar Mahor (AAPS PharmSciTech, 2025)

Combined effect of mercury and ammonia toxicity and its mitigation through selenium nanoparticles in fish - Anupama Shinde; Rajesh Sharma; Prem Kumar; Tarkeshwar Kumar; Kotha Sammi Reddy; Neeraj Kumar (Aquatic Toxicology, 2025)

Sustainable microbial solutions for managing fungal threats in wheat: progress and future directions - Prem Lal Kashyap; Sudheer Kumar; Annie Khanna; Poonam Jasrotia; Gyanendra Singh (World Journal of Microbiology and Biotechnology, 2025)

Translating molecular insights into clinical success: alkaloid-based therapies for leukemia - Pouya Goleij; Mohammad Amin Khazeei Tabari; Aryan Rezaee; Pantea Majma Sanaye; Maria Daglia; Dorsa Alijanzadeh; Khalaf F. Alsharif; Alan Prem Kumar; Haroon Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Strength and microstructural characteristics of sustainable aluminosilicate binder using waste glass powder and ground granulated blast furnace slag - P. Manikandan; V. Prem Kumar; V. Vasugi (Innovative Infrastructure Solutions, 2025)

Biochar for mitigating pharmaceutical pollution in wastewater: A sustainable solution - Sampurna Nand; Prem Prakash Singh; Swati Verma; Sandhya Mishra; Anju Patel; Siddharth Shukla; Pankaj Kumar Srivastava (Science of The Total Environment, 2025)

Design and analyses of an AB5 - metal hydride based canister for hydrogen compressor application - Kakumanu Suvarna Jaya Prakash; K.Kishor Kumar; Vinod Kumar Sharma; Prem Kumar Chaurasiya; Tikendra Nath Verma; Anoop Kumar Shukla; Gaurav Dwivedi (Process Safety and Environmental Protection, 2025)

Effects of Moringa oleifera seed extract on growth and immunophysiology of whisker catfish (Mystus gulio) fingerlings - Prangya Parimita Panda; Prem Kumar; Bairagi Charan Mallick; Neeraj Kumar; Tapas Kumar Ghoshal (Fish Physiology and Biochemistry, 2025)

Factors affecting smallholder farmers’ adaptive capacity to climate change: A comparative study of Nepal, India, and Bangladesh - Prem Sagar Chapagain; Tibendra Raj Banskota; Shobha Shrestha; Yili Zhang; Jianzhong Yan; Suresh Chand Rai; Md Nurul Islam; Linshan Liu; Umesh Kumar Mandal; Basanta Paudel; Narendra Raj Khanal; Om Chandra Thasineku (Journal of Geographical Sciences, 2025)

Fruit and pulse synergy: evaluating Vigna mungo performance in Himalayan wild pomegranate based agroforestry systems - Avinash Kumar Bhatia; K. S. Pant; Prem Prakash; Praveen Kumar; Harish Sharma; Saakshi; Prakash; Babita Kumari (Agroforestry Systems, 2025)

Suitability analysis for agroforestry in District Hamirpur of Himachal Pradesh, India by using AHP method - Avinash Kumar Bhatia; Saakshi Chauhan; Kashmir Singh Pant; Maneesh Singh Bhandari; Prem Prakash Sharma; Parveen Kashyap (Agroforestry Systems, 2025)

Artificial intelligence integration in conventional wastewater treatment techniques: techno-economic evaluation, recent progress and its future direction - B. Senthil Rathi; P. Senthil Kumar; S. Sanjay; M. Prem Kumar; Gayathri Rangasamy (International Journal of Environmental Science and Technology, 2025)

Phytophagous probiotic foods: Exploring the intersection of characteristics, quality implications, health benefits, and market dynamics - Alaa Kareem Niamah; Shayma Thyab Gddoa Al-Sahlany; Hussein Katai Abdul-Sada; Pawan Prabhakar; Soubhagya Tripathy; Basant Kumar Dadrwal; Smita Singh; Deepak Kumar Verma; Alok Kumar Gupta; Rakesh Mohan Shukla; Mamta Thakur; Ami R. Patel; et al. (Trends in Food Science & Technology, 2024)

Impact of Different Tillage and Residue Retention Practices on Soil Nutrients, Microbial Community Composition and Grain Yield of Malt Barley - Om Parkash Ahlawat; Anil Khippal; Karnam Venkatesh; Rajender Singh Chhokar; Subhash Chander Gill; Prem Lal Kashyap; Ajit Singh Kharub; Lokendra Kumar; Neeraj Kumar; Anu Sharma; Kamini Kumari; Sonia Sheoran; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Formalin adulteration in fish: A state-of-the-art review on its prevalence, detection advancements, and affordable device innovations - Gurveer Kaur; Soubhagya Tripathy; Srutee Rout; Gayatri Mishra; Brajesh Kumar Panda; Prem Prakash Srivastav (Trends in Food Science & Technology, 2024)

Improper dietary protein to carbohydrate ratio causes abnormal visceral fat deposition, hampering gonadal development and breeding performance in Labeo Catla female - Uday Kumar Udit; Prem Kumar Meher; Nitish Kumar Chandan; Narinder Kumar Chadha; Paramita Banerjee Sawant; Jitendra Kumar Sundaray; Kanta Das Mahapatra; Padmanav Routray; Debajit Sarma; Samiran Nandi (Animal Feed Science and Technology, 2024)

Symbiotic orchestra: Tripartite ecology building by scalable microfluidics nano-fibre for sustainable cultivation - Bandana Kumari Sahu; Kamaljit Kaur; Debasis Mitra; Vibhav Katoch; Prem Kumar; Navjot Singh; Deepa Singh; Rita Choudhary; Amaresh Kumar Nayak; Bhanu Prakash; Periyasamy Panneerselvam; VijayaKumar Shanmugam (Chemical Engineering Journal, 2024)

Ancistrobrevinium A, the first N -methylated, cationic naphthylisoquinoline alkaloid, from the tropical liana Ancistrocladus abbreviatus (Ancistrocladaceae) - Nasir Tajuddeen; Shaimaa Fayez; Prem Prakash Kushwaha; Doris Feineis; Laurent Aké Assi; Shashank Kumar; Gerhard Bringmann (Natural Product Research, 2024)

Engineering the physical properties and photocatalytic activities of a β-ketoenamine COF using continuous flow synthesis - Astha Singh; Rituporn Gogoi; Kajal Sharma; Swadhin Kumar Jena; Rajesh Kumar; Najla Fourati; Chouki Zerrouki; Samy Remita; Prem Felix Siril (Chemosphere, 2024)

Bio-active essential oils derived from medicinal plants and their insecticidal potential on houseflies and cockroaches - Chinnaperumal Kamaraj; Rajappan Chandra Satish Kumar; Khalid A. Al-Ghanim; Selvam Naveenkumar; Pradisha Prem (South African Journal of Botany, 2024)

Assessment of phenological growth stages of Malaxis acuminata D. Don: a high value herbaceous medicinal plant - Kalpana Rautela; Yogita Bisht; Ashish Kumar; Arun K. Jugran; Indra D. Bhatt; Prem Prakash (Genetic Resources and Crop Evolution, 2024)

Predict the characteristics of the DI engine with various injection timings by Glycine max oil biofuel using artificial neural networks - Upendra Rajak; Manoj Panchal; Abhishek Dasore; Tikendra Nath Verma; Prem Kumar Chaurasiya (Environmental Science and Pollution Research, 2024)

Insights into the physicochemical, crystalline, multistructural, thermal and digestibility behavior of taro starch (Colocasia esculenta) modified by cold plasma treatment with high voltage dielectric barrier discharge (HVDBD): An alternative technique for chemical modification of starch and environmental sustainability - Rakesh Kumar Gupta; Proshanta Guha; Prem Prakash Srivastav (Journal of Cleaner Production, 2024)

Fine mapping of interspecific secondary CSSL populations revealed key regulators for grain weight at qTGW3.1 locus from Oryza nivara - Malathi Surapaneni; Divya Balakrishnan; Krishnamraju Addanki; Venkateswara Rao Yadavalli; Arun Prem Kumar; P. Prashanthi; R. M. Sundaram; Sarla Neelamraju (Physiology and Molecular Biology of Plants, 2024)

Insights into the influence of partial disease resistance components on host preference of Bipolaris sorokiniana in wheat - Sunanda Chakraborty; Sunita Mahapatra; Anubhab Hooi; Sk Hasibul Alam; Satish Kumar; Prem Lal Kashyap (Journal of Plant Pathology, 2024)

Insight into the role of metal support interface on shape dependent MnO2 support through the synergistic effect between Ag and MnO2 for the total oxidation of propane - Vijayanand Perupogu; Rajesh Rajendiran; Putrakumar Balla; Prem Kumar Seelam; Assa Aravindh; Sungtak Kim; Srinivasa Rao Pinapati; Lingaiah Nakka (Journal of Environmental Chemical Engineering, 2024)

Assessment of Trachyspermum ammi essential oil against Aspergillus flavus, aflatoxin B1 contamination, and post-harvest quality of Sorghum bicolor - Prem Pratap Singh; Atul Kumar Jaiswal; Ritu Singh; Akshay Kumar; Vishal Gupta; Tanya Singh Raghuvanshi; Angad Sharma; Bhanu Prakash (Food Chemistry, 2024)

A Multivariate Geomorphometric Approach to Prioritize Drought Prone Sakri Basin for Land and Water Resource Management - Pawan Jeet; Anil Kumar Singh; Ashutosh Upadhyaya; Anup Das; Rakesh Kumar; Prem Kumar Sundaram; Arti Kumari; Kirti Saurabh; Deepak Singh; Prem Pal Kumar (Journal of the Indian Society of Remote Sensing, 2024)

Exploring the effects of diverse extraction methods on nanoemulsion formulation using betel leaf essential oil: Assessing antibacterial efficacy against pathogenic microorganisms - Sangeetha Karunanithi; Rakesh Kumar Gupta; Proshanta Guha; Prem Prakash Srivastav (Food and Humanity, 2024)

Optimizing soybean biofuel blends for sustainable urban medium-duty commercial vehicles in India: an AI-driven approach - Upendra Rajak; Prem Kumar Chaurasiya; Tikendra Nath Verma; Abhishek Dasore; Ümit Ağbulut; Kundan Meshram; CAhamed Saleel; Shaik Saboor; Erdem Cuce; Zhibao Mian (Environmental Science and Pollution Research, 2024)
This article presents the outcomes of a research study focused on optimizing the performance of soybean biofuel blends derived from soybean seeds specifically for urban medium-duty commercial vehicles. The study took into consideration elements such as production capacity, economics and assumed engine characteristics. For the purpose of predicting performance, combustion and emission characteristics, an artificial intelligence approach that has been trained using experimental data is used. At full load, the brake thermal efficiency (BTE) dropped as engine speed increased for biofuel and diesel fuel mixes, but brake-specific fuel consumption (BSFC) increased. The BSFC increased by 11.9% when diesel compared to using biofuel with diesel blends. The mixes cut both maximum cylinder pressure and $${{\text{NO}}}_{{\text{x}}}$$ NO x emissions. The biofuel-diesel fuel proved more successful, with maximum reduction of 9.8% and 22.2 at rpm, respectively. The biofuel and diesel blend significantly improved carbon dioxide ( $${{\text{CO}}}_{2}$$ CO 2 ) and smoke emissions. The biofuel blends offer significant advantages by decreeing exhaust pollutants and enhancing engine performance. Graphical Abstract

Fabrication of dual S-scheme based CuWO4/NiFe/WO3 heterojunction for visible-light-induced degradation and reduction applications - Rohit Sharma; Nasarul Islam; Aashish Priye; Deepak Kumar; Jay Singh; Manish Kumar; Prem P. Sharma; Vinay Chauhan; Pooja Shandilya (Journal of Environmental Chemical Engineering, 2024)

Mechanically pulverized covalent organic framework as a metal-free photocatalyst for fenton-like degradation of organic pollutants and hexavalent chromium reduction - Rituporn Gogoi; Swadhin Kumar Jena; Astha Singh; Kajal Sharma; Kirti Khanna; Sumanta Chowdhury; Rajesh Kumar; Prem Felix Siril (Journal of Environmental Chemical Engineering, 2024)

Insight into the role of metal support interface through the synergistic effect between Ag and α-Bi2Mo3O12 support for the selective oxidation of propylene to acrolein - Rajesh Rajendiran; Putrakumar Balla; Prem Kumar Seelam; Assa Aravindh; Ravi Balaga; Karuppiah Alagusundari; Arunkumar Patchaiyappan; Sungtak Kim; Hou Wen Che; Natarajan Arumugam; Venkatesan Rengarajan; Ulla Lassi; et al. (Chemical Engineering Journal, 2024)

Challenges and mitigation strategies associated with Burkholderia cepacia complex contamination in pharmaceutical manufacturing - Sethuraman Prem Kumar; Karupanagounder Thangaraj Uthra; Vellapandian Chitra; Narayanasamy Damodharan; Gururaja Perumal Pazhani (Archives of Microbiology, 2024)

Seismic Imaging Along Alampur–Koniki–Ganapeswaram Profile, North Cuddapah Basin (India) and East Antarctica Correlation - K. Chandrakala; O. P. Pandey; Biswajit Mandal; K. Renuka; N. Prem Kumar (Pure and Applied Geophysics, 2024)

In vitro and In silico evaluation of the antioxidant, anti-microbial and antihyperglycemic properties of giloy (Tinospora cordifolia L.) stem extract - Kimmy; Deepak Kumar Verma; Pawan Prabhakar; Soubhagya Tripathy; Basant Kumar Dadrwal; Pradyuman Kumar; Prem Prakash Srivastav; Mamoni Banerjee (Biocatalysis and Agricultural Biotechnology, 2024)

Environmental challenges and concurrent trend of weather extremes over Uttarakhand Himalaya - Pramod Kumar; Arbind Patel; Jaya Rai; Prem Kumar (Theoretical and Applied Climatology, 2024)

Application of optimized bamboo fibre reinforced mortar in prefabricated bamboo reinforced wall panels as a sustainable building component - V. Prem Kumar; V. Vasugi (European Journal of Environmental and Civil Engineering, 2024)

Drug target therapy and emerging clinical relevance of exosomes in meningeal tumors - Swati Sharma; Rashmi Rana; Prem Prakash; Nirmal Kumar Ganguly (Molecular and Cellular Biochemistry, 2024)

Insights into the antimicrobial efficacy of Coleus aromaticus essential oil against food-borne microbes: Biochemical and molecular simulation approaches - Prem Pratap Singh; Atul Kumar Jaiswal; Tanya Singh Raghuvanshi; Bhanu Prakash (Food and Chemical Toxicology, 2023)

Soil respiration under different N fertilization and irrigation regimes in Bengaluru, S-India - Suman Kumar Sourav; C. T. Subbarayappa; D C. Hanumanthappa; Mudalagiriyappa; Prem Jose Vazhacharickal; Andrea Mock; Mariko Ingold; Andreas Buerkert (Nutrient Cycling in Agroecosystems, 2023)
Rapid urbanization in many countries of the Global South has led to intensification of urban and peri-urban agriculture (UPA) whose effects on the soils’ physical, chemical, and microbial properties have been hardly studied. We therefore investigated the effects of different intensity levels, exemplified by three rates of mineral nitrogen (N) addition and irrigation on CO 2 emissions in typical crops during the wet ( Kharif ) and dry ( Rabi ) season on a Nitisol in Bengaluru, S-India. Respiration data were collected from 2017 to 2021 in two two-factorial split-plot experiments conducted under rainfed and irrigated conditions. Test crops were maize ( Zea mays L.), finger millet ( Eleusine coracana Gaertn.), and lablab ( Lablab purpureus L. Sweet) under rainfed and irrigated conditions, as well as the vegetables cabbage ( Brassica oleracea var. capitata ), eggplant ( Solanum melongena L.), and tomato ( Solanum lycopersicum L.) or chili ( Capsicum annuum L.). Carbon dioxide (CO 2 ) emissions were determined using a Los Gatos Research (LGR) multi-gas analyzer whereby under our study conditions CH 4 , NH 3 and N 2 O were negligible. Measurements were conducted from 7:00 am to 11:30 am and repeated from 12:30 pm to 6:00 pm. Irrespective of irrigation, season, crops and N fertilizer level, CO 2 emission rates during afternoon hours were significantly higher (2–128%) than during morning hours. In the irrigated field diurnal emission differences between afternoon and morning hours ranged from 0.04 to 1.61 kg CO 2 -C ha −1 h −1 while in the rainfed field they averaged 0.20–1.78 kg CO 2 -C ha −1 h −1 . Irrespective of crops, in the rainfed field CO 2 emissions in high N plots were 56.4% larger than in low N plots whereas in the irrigated field they were only 12.1% larger. The results of a linear mixed model analysis indicated that N fertilization enhanced CO 2 emissions whereby these effects were highest in rainfed crops. Soil moisture enhanced emissions in rainfed crops but decreased them under irrigation where crop-specific CO 2 emissions within a season were independent of N application. Soil temperature at 5 cm depth enhanced CO 2 emissions in both fields. Overall, higher N and soil temperature enhanced CO 2 fluxes whereas effects of soil moisture depended on irrigation.

A correlational study of uranium in groundwater with other physicochemical parameters using GIS mapping in Godda district of Jharkhand, India - Mansi Srivastava; Prem Kumar Srivastava (Environmental Geochemistry and Health, 2023)

Fatty acid mobilization and histological changes at different maturation stages of female hilsa, Tenualosa ilisha - Prem Kumar; Nitish Kumar Chandan; G. Biswas; Babita Mandal; T. Hussain; M. Kailasam; K.P. Jithendran (Aquaculture, 2023)

Mineralogy, geochemistry and genesis of the polymetallic crusts from the Chagos-Laccadive Ridge, Arabian Sea, India - Saju Varghese; H. Angeshri Manohar; Sharika Mathew; K.N. Noufal; Rachna Pillai; C.V. Gopalan; Pankaj Kumar; Prem Chand Kisku; R.V. Vairavan; Smitha Joseph; Kalarani; Soumya Vijayan; et al. (Marine Geology, 2023)

Continuous flow synthesis of visible light-active conjugated porous polymer for pollutant degradation and plastic waste photoreforming - Astha Singh; Rituporn Gogoi; Kajal Sharma; Swadhin Kumar Jena; Najla Fourati; Chouki Zerrouki; Samy Remita; Prem Felix Siril (Journal of Cleaner Production, 2023)

Studies on natural regeneration, floristic composition, biomass, carbon density and soil properties along an altitudinal gradient in the north-western Himalayas, India - Ghanshyam Singh; Vimal Chauhan; C.L. Thakur; M.L. Verma; Rohit Bishist; Prem Prakash; Krishan Lal Gautam; Harish Sharma; Rushal Dogra; Kamal Kishore; Munesh Kumar (Forest Ecology and Management, 2023)

nth order kinetic modelling of peroxidase and polyphenol oxidase inactivation in kiwifruit juice during cold plasma and thermal treatment - Sitesh Kumar; Sunil Pipliya; Prem Prakash Srivastav (Innovative Food Science & Emerging Technologies, 2023)

Agricultural intensification effects on spatial growth variability of staple crops in south India - Andreas Buerkert; Hans-Peter Piepho; Suman Kumar Sourav; Ellen Hoffmann; Prem Jose Vazhacharickal; Chickadibburahalli T. Subbarayappa; Michael Wachendorf (Field Crops Research, 2023)

Nanoencapsulation of biofunctional components as a burgeoning nanotechnology-based approach for functional food development: A review - Soubhagya Tripathy; Deepak Kumar Verma; Alok Kumar Gupta; Prem Prakash Srivastav; Ami R. Patel; Mónica L. Chávez González; Gemilang Lara Utama; Cristobal Noe Aguilar (Biocatalysis and Agricultural Biotechnology, 2023)

Blue lotus (Nymphaea nouchali) flower and leaf supplements enhance growth and hemato-immunological parameters in Indian major carp (Labeo rohita) juveniles - Sanayaima Singha; Shivendra Kumar; Sujit Kumar Nayak; Pravesh Kumar; Aditi Banik; Prem Prakash Srivastava (Animal Feed Science and Technology, 2023)

CXCR4 expression is elevated in TNBC patient derived samples and Z-guggulsterone abrogates tumor progression by targeting CXCL12/CXCR4 signaling axis in preclinical breast cancer model - Nikita Gupta; Chakrabhavi Dhananjaya Mohan; Muthu K. Shanmugam; Young Yun Jung; Arunachalam Chinnathambi; Sulaiman Ali Alharbi; Milad Ashrafizadeh; Manas Mahale; Andreas Bender; Alan Prem Kumar; Thomas Choudary Putti; Kanchugarakoppal S. Rangappa; et al. (Environmental Research, 2023)

Growth Stage-Dependent Foliar Application of Iron Improves its Mobilisation Towards Grain and Enhances Fe Use Efficiency in Rice - Sandeep Sharma; Renu Pandey; Christian O. Dimkpa; Arun Kumar; Prem S. Bindraban (Journal of Plant Growth Regulation, 2023)

Influence of short- and long-term persistence on identification of rainfall temporal trends using different versions of the Mann-Kendall test in Mizoram, Northeast India - Vanita Pandey; Pankaj Kumar Pandey; Bivek Chakma; Prem Ranjan (Environmental Science and Pollution Research, 2023)

Bacterial volatiles as PGPRs: Inducing plant defense mechanisms during stress periods - Rajat Laller; Prem Kumar Khosla; Nidhi Negi; Harish Avinash; Kusum; Nitika Thakur; Shashank Kashyap; Sudheesh K. Shukla; Iqtidar Hussain (South African Journal of Botany, 2023)

Mapping hotspot clustering: An approach to study the spatial pattern of quality of living households in India - Venkatesh Ravichandran; Komali Kantamaneni; Aditya Singh; Aishwarya Nair; Janakiraman A; Sukumar Prem Kumar; Shubham Dhar Choudhury (Remote Sensing Applications: Society and Environment, 2023)

Evaluation of the reduction in greenhouse gas emissions attributable to wind energy: A retrospective evaluation of Indian Offshore and Coastal Site - Prem Kumar Chaurasiya; Harsh Patidar; Vikas Shende; Upendra Rajak; Tikendra Nath Verma; Gaurav Dwivedi (Ocean Engineering, 2023)

The role of AgNPs in selective oxidation of benzyl alcohol in vapor phase using morphologically tailored MnO2 nanorods in the presence of air - Rajesh Rajendiran; Shrutika Lingalwar; Assa Aravindh; Alagusundari Karuppiah; Putrakumar Balla; Prem Kumar Seelam; B. Shanmugavelu; Vijayanand Perupogu; Sungtak Kim; Ulla Lassi (Chemical Engineering Journal, 2023)

Effects of feeding frequency on growth, survival, body composition and size variation in long whiskers catfish, Mystus gulio (Hamilton, 1822) fry reared in net cage system - Gouranga Biswas; Prem Kumar; Babita Mandal; Tapas K. Ghoshal; Debasis De; Aritra Bera; M. Kailasam (Regional Studies in Marine Science, 2023)

Effects of CuO/Al2O3/Water-WO3 nanomaterials on NETZERO energy/emission-based hydrogen generation - T. Sathish; R. Saravanan; T. Vijay Muni; G.A. Sivasankar; J. Prem Kumar; M. Rajasimman; Yasser Vasseghian; Y.-K. Park (Fuel, 2023)

Characterization, catalytic, and recyclability studies of nano-sized spherical palladium particles synthesized using aqueous poly-extract (turmeric, neem, and tulasi) - Aditya Velidandi; Mounika Sarvepalli; Pradeep Kumar Gandam; Ninian Prem Prashanth Pabbathi; Rama Raju Baadhe (Environmental Research, 2023)

Design of catamaran type fish feeder for aquaculture applications - Ritu Prem; Vishwanath Nagarajan; Virendra Kumar Tewari (Ocean Engineering, 2023)

Induction of rosmarinic acid in callus cultures of Ocimum sanctum - Vijay Kumar Dalal; Prem Kumar Dantu (Journal of Plant Biochemistry and Biotechnology, 2023)

The green seaweed, Enteromorpha intestinalis: An efficient inorganic extractive species for environmental remediation and improved performances of fed species in brackishwater integrated multi-trophic aquaculture (BIMTA) system - Sanchita Naskar; Gouranga Biswas; Prem Kumar; Debasis De; Sanjoy Das; Paramita Banerjee Sawant; Narinder K. Chadha; Preetimayee Behera (Aquaculture, 2023)

Combustion, performance, and emission behavior of a CI engine fueled with different biodiesels: A modelling, forecasting and experimental study - Vivek Kumar Nema; Alok Singh; Prem Kumar Chaurasiya; Tapan Kumar Gogoi; Tikendra Nath Verma; Damodar Tiwari (Fuel, 2023)

Groundwater spring potential zonation using AHP and fuzzy-AHP in Eastern Himalayan region: Papum Pare district, Arunachal Pradesh, India - Prem Ranjan; Pankaj Kumar Pandey; Vanita Pandey (Environmental Science and Pollution Research, 2023)

A systematic review on endophytic fungi and its role in the commercial applications - Reema Devi; Rachna Verma; Rajni Dhalaria; Ashwani Kumar; Dinesh Kumar; Sunil Puri; Monika Thakur; Saurav Chauhan; Prem Parkash Chauhan; Eugenie Nepovimova; Kamil Kuca (Planta, 2023)

Erratum to “Temporal expression profiling of GhNAC transcription factor genes in cotton cultivars under abiotic stresses” [Plant Gene 28C (2021) 100334] - S. Sivakumar; G. Prem Kumar; S. Vinoth; G. Siva; M. Vigneswaran; P. Gurusaravanan; M. Kanakachari; T. Senthil Kumar; P. Baskaran; N. Jayabalan (Plant Gene, 2023)

Influence of ultrasonic application on soybean aqueous extract based composite edible film: Characterization and their food application - Vanisseri Ajesh Kumar; M. Pravitha; Ajay Yadav; R. Pandiselvam; Prem Prakash Srivastav (Food Hydrocolloids, 2023)

Correlation of biological activities of bark and leaves of Terminalia arjuna collected from different geographical regions of Himachal Pradesh, India - Vikas Kumar; Nitin Sharma; Anuradha Sourirajan; Prem Kumar Khosla; Kamal Dev (Biochemical Systematics and Ecology, 2023)

Experimental testing of solar-based air heater roughed with discrete V-down rib and staggered element - Piyush Kumar Jain; Atul Lanjewar; Prem Kumar Chaurasiya; Damodar Tiwari; Vinod Kumar Sharma (Environmental Science and Pollution Research, 2023)

Laboratory set-up for surface hoar layer growth over rounded grain snow - Chaman Chandel; Praveen K. Srivastava; Vinod Kumar; Prem Datt; Rahul Sheoran; P.K. Satayawali (Cold Regions Science and Technology, 2023)

Morphologically tailored facet dependent silver nanoparticles supported α-Al2O3 catalysts for chemoselective reduction of aromatic nitro compounds - Rajesh Rajendiran; Prem Kumar Seelam; Arunkumar Patchaiyappan; Putrakumar Balla; Harisingh Shankar; Balaga Ravi; Vijayanand Perupogu; Ulla Lassi (Chemical Engineering Journal, 2023)

Morpho-physiological and demographic responses of three threatened Ilex species to changing climate aligned with species distribution models in future climate scenarios - Prem Prakash Singh; Mukunda Dev Behera; Richa Rai; Uma Shankar; Krishna Upadhaya; Ibadahun Mary Nonghuloo; Aabid Hussain Mir; Sushmita Barua; Mariya Naseem; Pankaj Kumar Srivastava; Raghuvar Tiwary; Anita Gupta; et al. (Environmental Monitoring and Assessment, 2023)

Effects of microalgae -ethanol-methanol-diesel blends on the spray characteristics and emissions of a diesel engine - Upendra Rajak; Abhishek Dasore; Prem Kumar Chaurasiya; Tikendra Nath Verma; Prerana Nashine; Anil Kumar (Environment, Development and Sustainability, 2023)

Gonad recrudescence and annual sex steroid patterns in female goldspot mullet, Liza parsia reared in brackishwater pond - Prem Kumar; P. Behera; G. Biswas; T.K. Ghoshal; Sanjoy Das; M. Kailasam; K.P. Jithendran (Animal Reproduction Science, 2023)

Molecular diversity, haplotype distribution and genetic variation flow of Bipolaris sorokiniana fungus causing spot blotch disease in different wheat-growing zones - Prem Lal Kashyap; Sudheer Kumar; Anju Sharma; Ravi Shekhar Kumar; Sunita Mahapatra; Noyonika Kaul; Annie Khanna; Poonam Jasrotia; Gyanendra Pratap Singh (Journal of Applied Genetics, 2022)

Effect of Astaxanthin and Copper Supplementation on Growth, Immunity, Antioxidant, and Blood Biochemical Status of Growing Murrah Buffalo Heifers - Rajesh Kumar; Deo Saran Sahu; Gulab Chandra; Satya Prakash Yadav; Raj Kumar; Nazim Ali; Debashis Roy; Prem Sagar Maurya (Biological Trace Element Research, 2022)

Downstream processing of biomass produced in aquaculture wastewater for valuable pigments from the cyanobacterium Spirulina (Arthrospira) platensis: a green and sustainable approach - Gardiyawasam Pussewalage Wineetha A Prabhath; Satya Prakash Shukla; Prem Prakash Srivastava; Kundan Kumar; Paramita Banerjee Sawant; Ajit Kumar Verma; Mithlesh Kumar Chouksey; Kithulampitiya Koralege Tharaka Nuwansi (Aquaculture International, 2022)

Correction to: A reservoir evolution model of synrift lacustrine hyperpycnites, Barmer Basin (Rajasthan, India) - Pinaki Majumdar; Shubhodip Konar; John Dolson; Archana Dhanasetty; Ajoy Krishna Bora; Prem Kumar (Arabian Journal of Geosciences, 2022)

Isolation, modification, and characterization of rice starch with emphasis on functional properties and industrial application: a review - Deepak Kumar Verma; Prem Prakash Srivastav (Critical Reviews in Food Science and Nutrition, 2022)

A reservoir evolution model of synrift lacustrine hyperpycnites, Barmer Basin (Rajasthan, India) - Pinaki Majumdar; Shubhodip Konar; John Dolson; Archana Dhanasetty; Ajoy Krishna Bora; Prem Kumar (Arabian Journal of Geosciences, 2022)

Toxicity ameliorative effect of vitamin E against super-paramagnetic iron oxide nanoparticles on haemato-immunological responses, antioxidant capacity, oxidative stress, and metabolic enzymes activity during exposure and recovery in Labeo rohita fingerlings - Munish Kumar; Gyandeep Gupta; Nuzaiba P. Muhammed; Karthik R; Tincy Varghese; Prem Prakash Srivastava; Shashi Bhushan; Satya Prakash Shukla; Gopal Krishna; Subodh Gupta (Aquaculture International, 2022)

Genetic admixture and population structure analysis of Indian water buffaloes (Bubalus bubalis) using STR markers - Surarapu Lava Kumar; Ravinder Singh; Ankita Gurao; S. K. Mishra; Prem Kumar; Vikas Vohra; Saket Kumar Niranjan; Monika Sodhi; S. K. Dash; S. Sarangdhar; Manishi Mukesh; Ranjit Singh Kataria (Molecular Biology Reports, 2022)

Withania somnifera phytochemicals possess SARS-CoV-2 RdRp and human TMPRSS2 protein binding potential - Kumari Sunita Prajapati; Atul Kumar Singh; Prem Prakash Kushwaha; Mohd Shuaib; Santosh Kumar Maurya; Sanjay Gupta; Sabyasachi Senapati; Surya Pratap Singh; Mohammad Waseem; Shashank Kumar (Vegetos, 2022)

Correction: The effects on performance and emission characteristics of DI engine fuelled with CeO2 nanoparticles addition in diesel/tyre pyrolysis oil blends - Upendra Rajak; Prerana Nashine; Prem Kumar Chaurasiya; Tikendra Nath Verma; Abhishek Dasore; Kamal Kishore Pathak; Gaurav Dwivedi; Anoop Kumar Shukla; Gaurav Saini (Environment, Development and Sustainability, 2022)

Self-Training with Spatially Confident and Diverse Samples for the Classification of Remote Sensing Images - Prem Shankar Singh Aydav; Vipin Kumar; Sonajharia Minz (Journal of the Indian Society of Remote Sensing, 2022)

Characterization of five new pathotypes of Puccinia triticina identified from Northeast India, Nepal, and Bangladesh - Subodh Kumar; Subhash Chander Bhardwaj; Om Prakash Gangwar; Pramod Prasad; Ranjana Chakrabarty; Prem Lal Kashyap; Hanif Khan; Siddanna Savadi; Baidya Nath Mahato; Paritosh Kumar Malaker (Australasian Plant Pathology, 2022)

The effects on performance and emission characteristics of DI engine fuelled with CeO2 nanoparticles addition in diesel/tyre pyrolysis oil blends - Upendra Rajak; Prerana Nashine; Prem Kumar Chaurasiya; Tikendra Nath Verma; Abhishek Dasore; Kamal Kishore Pathak; Gauav Dwivedi; Anoop Kumar Shukla; Gaurav Saini (Environment, Development and Sustainability, 2022)

Botanicals for Sustainable Management of Stored Food Grains: Pesticidal Efficacy, Mode of Action and Ecological Risk Assessment Using Computational Approaches - Bhanu Prakash; Prem Pratap Singh; Akshay Kumar; Vishal Gupta (Anthropocene Science, 2022)

Geotechnical and geological studies of Adit-6 of the railway tunnel between Rishikesh and Karnprayag in India focusing on the excavation methods and design of support analysis: a case study - Md Alquamar Azad; Somendra Kumar Singh; Apurva Alok; Meenakshi; Saurav Shekhar; Prem Kumar (Arabian Journal of Geosciences, 2022)

Evaluating the effects of carbon monoxide releasing molecule-2 against myocardial ischemia–reperfusion injury in ovariectomized female rats - Arthi Kumar; Sri Rahavi Boovarahan; Priyanka N. Prem; Meenakshi Ramanathan; David Raj Chellappan; Gino A. Kurian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Activin receptor type IIB in rohu (Labeo rohita): molecular characterization, tissue distribution and immunohistochemical localization during different stages of gonadal maturation - Siddhi Patnaik; Lakshman Sahoo; Mausumee Mohanty; Amrita Bit; Prem Kumar Meher; Sachidananda Das; Pallipuram Jayasankar; Jatindra Nath Saha; Paramananda Das (Fish Physiology and Biochemistry, 2021)

Dietary protein and lipid concentrations affect the growth, nutritional indices, and whole-body composition of long-whisker catfish, Mystus gulio, fry - Rooprekha Khatua; Kedar Nath Mohanta; Nitish Kumar Chandan; Rojalin Pattanayak; Choudhury Suryakant Mishra; Prem Kumar (Aquaculture International, 2021)

Comparative analysis of phytochemicals, antimicrobial and antioxidant activity of different species of Terminalia from Himachal Pradesh, India - Vikas Kumar; Shikha R. Chandel; Shikha Guleria; Nitin Sharma; Anuradha Sourirajan; Prem Kumar Khosla; Kamal Dev (Vegetos, 2021)

Characterization of phytochemicals and validation of antioxidant and anticancer activity in some Indian polyherbal ayurvedic products - Prem Prakash Kushwaha; Ramesh Kumar; Panchi Rani Neog; Malay Ranjan Behara; Pratibha Singh; Ajay Kumar; Kumari Sunita Prajapati; Atul Kumar Singh; Mohd Shuaib; Amit Kumar Sharma; Abhay Kumar Pandey; Shashank Kumar (Vegetos, 2021)

Enhancement in Plant Growth and Zinc Biofortification of Chickpea (Cicer arietinum L.) by Bacillus altitudinis - Prity Kushwaha; Ruchi Srivastava; Kuppusamy Pandiyan; Arjun Singh; Hillol Chakdar; Prem Lal Kashyap; Ajay Kumar Bhardwaj; Kumar Murugan; Nanjappan Karthikeyan; Samadhan Yuvraj Bagul; Alok Kumar Srivastava; Anil Kumar Saxena (Journal of Soil Science and Plant Nutrition, 2021)

Role of ZBTB7A zinc finger in tumorigenesis and metastasis - Atul Kumar Singh; Shiv Verma; Prem Prakash Kushwaha; Kumari Sunita Prajapati; Mohd Shuaib; Shashank Kumar; Sanjay Gupta (Molecular Biology Reports, 2021)

Homophilic and heterophilic cadherin bond rupture forces in homo- or hetero-cellular systems measured by AFM-based single-cell force spectroscopy - Prem Kumar Viji Babu; Ursula Mirastschijski; Ganzanfer Belge; Manfred Radmacher (European Biophysics Journal, 2021)
Cadherins enable intercellular adherens junctions to withstand tensile forces in tissues, e.g. generated by intracellular actomyosin contraction. In-vitro single molecule force spectroscopy experiments can reveal cadherin–cadherin extracellular region binding dynamics such as bond formation and strength. However, characterization of cadherin-presenting cell homophilic and heterophilic binding in the proteins’ native conformational and functional states in living cells has rarely been done. Here, we used atomic force microscopy (AFM) based single-cell force spectroscopy (SCFS) to measure rupture forces of homophilic and heterophilic bond formation of N- (neural), OB- (osteoblast) and E- (epithelial) cadherins in living fibroblast and epithelial cells in homo- and hetero-cellular arrangements, i.e., between cells and cadherins of the same and different types. In addition, we used indirect immunofluorescence labelling to study and correlate the expression of these cadherins in intercellular adherens junctions. We showed that N/N and E/E-cadherin homophilic binding events are stronger than N/OB heterophilic binding events. Disassembly of intracellular actin filaments affects the cadherin bond rupture forces suggesting a contribution of actin filaments in cadherin extracellular binding. Inactivation of myosin did not affect the cadherin rupture force in both homo- and hetero-cellular arrangements, but particularly strengthened the N/OB heterophilic bond and reinforced the other cadherins’ homophilic bonds.

Contributions of human ACE2 and TMPRSS2 in determining host–pathogen interaction of COVID-19 - SABYASACHI SENAPATI; PRATIBHA BANERJEE; SANDILYA BHAGAVATULA; PREM PRAKASH KUSHWAHA; SHASHANK KUMAR (Journal of Genetics, 2021)

Neutralizing antibody response against subcutaneously injected bacteriophages in rabbit model - Archana Archana; Prem Shankar Patel; Rajesh Kumar; Gopal Nath (VirusDisease, 2021)

Genomic analysis of a novel species Halomonas shambharensis isolated from hypersaline lake in Northwest India - Kapilesh Jadhav; Bijayendra Kushwaha; Indrani Jadhav; Prem Shankar; Anjali Geethadevi; Gaurav Kumar; Sonam Mittal; Guru Prasad Sharma; Madhuri Parashar; Deepak Parashar (Molecular Biology Reports, 2021)

β-Adrenoceptor blockade prevents carotid body hyperactivity and elevated vascular sympathetic nerve density induced by chronic intermittent hypoxia - Abdulaziz A. Alzahrani; Lily L. Cao; Hayyaf S. Aldossary; Demitris Nathanael; Jiarong Fu; Clare J. Ray; Keith L. Brain; Prem Kumar; Andrew M. Coney; Andrew P. Holmes (Pflügers Archiv - European Journal of Physiology, 2021)
Carotid body (CB) hyperactivity promotes hypertension in response to chronic intermittent hypoxia (CIH). The plasma concentration of adrenaline is reported to be elevated in CIH and our previous work suggests that adrenaline directly activates the CB. However, a role for chronic adrenergic stimulation in mediating CB hyperactivity is currently unknown. This study evaluated whether beta-blocker treatment with propranolol (Prop) prevented the development of CB hyperactivity, vascular sympathetic nerve growth and hypertension caused by CIH. Adult male Wistar rats were assigned into 1 of 4 groups: Control (N), N + Prop, CIH and CIH + Prop. The CIH paradigm consisted of 8 cycles h −1 , 8 h day −1 , for 3 weeks. Propranolol was administered via drinking water to achieve a dose of 40 mg kg −1 day −1 . Immunohistochemistry revealed the presence of both β 1 and β 2 -adrenoceptor subtypes on the CB type I cell. CIH caused a 2–3-fold elevation in basal CB single-fibre chemoafferent activity and this was prevented by chronic propranolol treatment. Chemoafferent responses to hypoxia and mitochondrial inhibitors were attenuated by propranolol, an effect that was greater in CIH animals. Propranolol decreased respiratory frequency in normoxia and hypoxia in N and CIH. Propranolol also abolished the CIH mediated increase in vascular sympathetic nerve density. Arterial blood pressure was reduced in propranolol groups during hypoxia. Propranolol exaggerated the fall in blood pressure in most (6/7) CIH animals during hypoxia, suggestive of reduced sympathetic tone. These findings therefore identify new roles for β-adrenergic stimulation in evoking CB hyperactivity, sympathetic vascular hyperinnervation and altered blood pressure control in response to CIH.

Novel amide analogues of quinazoline carboxylate display selective antiproliferative activity and potent EGFR inhibition - Anjleena Malhotra; Ranju Bansal; Clarissa Esmeralda Halim; Celestial T. Yap; Gautam Sethi; Alan Prem Kumar; Mahendra Bishnoi; Kamalendra Yadav (Medicinal Chemistry Research, 2020)

Identification, Characterization and Evaluation of Multifaceted Traits of Plant Growth Promoting Rhizobacteria from Soil for Sustainable Approach to Agriculture - Teg Bahadur Singh; Vikram Sahai; Deepika Goyal; Mrinalini Prasad; Arti Yadav; Preksha Shrivastav; Akbar Ali; Prem Kumar Dantu (Current Microbiology, 2020)

Elucidation of antifungal toxicity of Callistemon lanceolatus essential oil encapsulated in chitosan nanogel against Aspergillus flavus using biochemical and in-silico approaches - Prem Pratap Singh; Akshay Kumar; Bhanu Prakash (Food Additives & Contaminants: Part A, 2020)

Broodstock development and captive maturation of hilsa ( Tenualosa ilisha ) in a brackishwater pond‐based system - Debasis De; Panantharayil S. Shyne Anand; Suchita Mukherjee; Prem Kumar; Jagabathula Syama Dayal; Ramalingam Ananda Raja; Aritra Bera; Vettath Raghavan Suresh; Koyadan Kizhakedath Vijayan (Journal of Fish Biology, 2020)
Successful captive broodstock development of clupeid fish, hilsa, is one of the major challenges for the artificial propagation of this economically valued fish. The present study provides novel insights into the pond‐reared captive broodstock development of hilsa using artificial feed. In the present study, wild collected hilsa fry (weight 1.35 ± 0.13 g, length 53.84 ± 0.95 mm) were reared in grow‐out ponds for 6 months followed by maintaining them as broodstock in other ponds using formulated feed in both cases. After 6 months of pond rearing, the average body weight and length of fish were 66.76 ± 4.53 g and 184.75 ± 3.65 mm, respectively. In broodstock ponds, hilsa subadults fed with formulated feed (crude protein 41.06%) ensured significant advancement in ovarian maturity with gonado somatic index of 9.09%, enhanced secondary yolk stage oocytes of 91.66% and enlargement of oocyte diameters up to 570 μm. The broodstock reached somatic growth such as average body weight and average body length of 383.80 ± 27.38 g and 339.33 ± 9.68 mm, respectively, with a condition factor of 1.06 ± 0.15. Gut content analysis revealed the better acceptability of the artificial feed. Lipid profiling of muscle and ovary during gonadal maturation revealed mobilization of fat from muscle to ovary and selective retention of some fatty acids ( i.e. , C14:0, C18:0, C20:5, C22:6 and C20:4) in the ovary, which might help in gonadal maturation. Statement of Significance Successful rearing of wild‐caught hilsa juvenile in captive condition using formulated feed showed its potential as aquaculture species in low saline conditions. Advance stage of maturation in low saline captive conditions showed the possibility for induced breeding of hilsa, a high priced anadromous fish. Mobilization of fat from muscle to ovary and selective retention of some fatty acids in the ovary showed the scope of dietary manipulation for broodstock development of hilsa.

Identifying archaeological evidence of past earthquakes in a contemporary disaster scenario: case studies of damage, resilience and risk reduction from the 2015 Gorkha Earthquake and past seismic events within the Kathmandu Valley UNESCO World Heritage Property (Nepal) - Christopher Davis; Robin Coningham; Kosh Prasad Acharya; Ram Bahadur Kunwar; Paolo Forlin; Kai Weise; Prem Nath Maskey; Anie Joshi; Ian Simpson; David Toll; Sean Wilkinson; Paul Hughes; et al. (Journal of Seismology, 2020)
The 2015 Gorkha Earthquake was a humanitarian disaster but also a cultural catastrophe that damaged and destroyed historic monuments across Nepal, including those within the Kathmandu Valley UNESCO World Heritage Property. In the rush to rebuild, traditionally constructed foundations are being removed and replaced with modern materials without assessments of whether these contributed to the collapse of a monument. Generally undertaken without scientific recording, these interventions have led to the irreversible destruction of earlier subsurface phases of cultural activity and the potential loss of evidence for successful traditional seismic adaptations and risk reduction strategies, with no research into whether modern materials, such as concrete and steel, would offer enhanced resilience. In response to this context, multidisciplinary post-disaster investigations were undertaken between 2015 and 2018, including archaeological excavation, geophysical survey, geoarchaeological analysis, linked to architectural and engineering studies, to begin to evaluate and assess the damage to, and seismic adaptations of, historic structures within Nepal’s Kathmandu Valley. Where possible, we draw on archaeoseismological approaches for the identification and classification of Earthquake Archaeological Effects (EAEs) at selected monuments damaged by the 2015 Gorkha Earthquake. Lessons learned from evidence of potential weaknesses, as well as historic ‘risk-sensitive tactics’ of hazard reduction within monuments, are now being incorporated into reconstruction and rehabilitation initiatives alongside the development of methods for the protection of heritage in the face of future earthquakes.

Functional characterization of endophytic bacilli from pearl millet ( Pennisetum glaucum ) and their possible role in multiple stress tolerance - Prity Kushwaha; Prem Lal Kashyap; Pandiyan Kuppusamy; Alok Kumar Srivastava; Rajesh Kumar Tiwari (Plant Biosystems, 2020)

Metamorphosed Banded Iron Formation of Gorumahisani-Sulaipat-Badampahar belt, in Precambrian Iron Ore Group, Singhbhum Craton, India: ore petrography, micro-chemical and genetic studies - Prasant Kumar Nayak; Patitapaban Mishra; Birendra Kumar Mohapatra; Prem Prakash Singh (Arabian Journal of Geosciences, 2020)

Experimental, numerical and field study investigating a heritage structure collapse after the 2015 Gorkha earthquake - Ashutosh Kumar; Paul N. Hughes; Vasilis Sarhosis; David Toll; Sean Wilkinson; Robin Coningham; Kosh Prasad Acharya; Kai Weise; Annie Joshi; Christopher Davis; Ram Bahadur Kunwar; Prem Nath Maskey (Natural Hazards, 2020)
This paper presents an investigation of the collapse of a 325-year-old multi-tiered heritage temple during the 2015 Gorkha earthquake in Kathmandu, Nepal. The research comprises a reconnaissance survey followed by a geotechnical investigation and numerical back-analysis carried out to understand the potential causes of the collapse. The assessment of the structural configuration of the temple indicated seismic vulnerability in the design due to the presence of discontinuous columns over the height of the temple and age-weakened bonding in the masonry walls. The geotechnical investigation revealed the presence of competent soil strata at the location, assisting the survey which indicated no differential or excessive settlement in the foundation. A series of cyclic triaxial tests were conducted on samples recovered during the geotechnical investigation to determine dynamic behaviour of the soil. Further, dynamic analysis of the plinth of the temple under the recorded acceleration–time history indicated a maximum drift percentage of 1.4% and residual relative displacement of 32 mm suggesting the potential reason behind the collapse. The output of this research will support seismic rehabilitation of ancient structures within World Heritage sites across Nepal and effective action plans to safeguard them against future earthquake hazard.

Biocontrol Potential of Salt-Tolerant Trichoderma and Hypocrea Isolates for the Management of Tomato Root Rot Under Saline Environment - Prem Lal Kashyap; Manoj Kumar Solanki; Prity Kushwaha; Sudheer Kumar; Alok Kumar Srivastava (Journal of Soil Science and Plant Nutrition, 2020)

Plant growth promoting and antifungal activity in endophytic Bacillus strains from pearl millet (Pennisetum glaucum) - Prity Kushwaha; Prem Lal Kashyap; Alok Kumar Srivastava; Rajesh Kumar Tiwari (Brazilian Journal of Microbiology, 2020)

Bacterial endophyte mediated plant tolerance to salinity: growth responses and mechanisms of action - Prity Kushwaha; Prem Lal Kashyap; Ajay Kumar Bhardwaj; Pandiyan Kuppusamy; Alok Kumar Srivastava; Rajesh Kumar Tiwari (World Journal of Microbiology and Biotechnology, 2020)

Isolation and Characterization of Endophytic Bacteria from Piper longum - Mubashar Nazir Mintoo; Sushma Mishra; Prem Kumar Dantu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Molecular detection and in silico characterization of cold shock protein coding gene (cspA) from cold adaptive Pseudomonas koreensis - Srikant Awasthi; Anjney Sharma; Pragya Saxena; Jagriti Yadav; K. Pandiyan; M. Kumar; Arjun Singh; Hillol Chakdar; Arpan Bhowmik; Prem L. Kashyap; Alok K. Srivastava; Anil K. Saxena (Journal of Plant Biochemistry and Biotechnology, 2019)

Chemical synthesis, molecular modeling and pharmacophore mapping of new pyrrole derivatives as inhibitors of InhA enzyme and Mycobacterium tuberculosis growth - Shrinivas D. Joshi; S. R. Prem Kumar; Sonali Patil; M. Vijayakumar; Venkatarao H. Kulkarni; Mallikarjuna N. Nadagouda; Aravind M. Badiger; Christian Lherbet; Tejraj M. Aminabhavi (Medicinal Chemistry Research, 2019)

Characterization of three new Yr9-virulences and identification of sources of resistance among recently developed Indian bread wheat germplasm - Om Prakash Gangwar; Subodh Kumar; Subhash Chander Bhardwaj; Prem Lal Kashyap; Pramod Prasad; Hanif Khan (Journal of Plant Pathology, 2019)

Optimized in vitro micro-tuber production for colchicine biosynthesis in Gloriosa superba L. and its anti-microbial activity against Candida albicans - Sivakumar Subiramani; Sathish Sundararajan; Siva Govindarajan; Vinoth Sadasivam; Prem Kumar Ganesan; Gurusaravanan Packiaraj; Vigneswaran Manickam; Senthil Kumar Thiruppathi; Sathishkumar Ramalingam; Jayabalan Narayanasamy (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Foliar Application of Iron Fortified Bacteriosiderophore Improves Growth and Grain Fe Concentration in Wheat and Soybean - Sandeep Sharma; Subhash Chandra; Arun Kumar; Prem Bindraban; Anil Kumar Saxena; Veena Pande; Renu Pandey (Indian Journal of Microbiology, 2019)

Forest biomass estimation using remote sensing and field inventory: a case study of Tripura, India - Prem Chandra Pandey; Prashant K. Srivastava; Tilok Chetri; Bal Krishan Choudhary; Pavan Kumar (Environmental Monitoring and Assessment, 2019)

Investigating the virulence and genetic diversity of Colletotrichum lindemuthianum populations distributed in the North Western Himalayan hill states - Naiya Sharma; Nidhi Kumari; Surinder Kumar Sharma; Bilal Ahmad Padder; Prem Nath Sharma (Journal of Plant Pathology, 2019)

Virulence and molecular analysis of atypical pathotypes of yellow rust pathogen in India - Om Prakash Gangwar; Subodh Kumar; Prem Lal Kashyap; Subhash Chander Bhardwaj; Pramod Prasad; Siddanna Savadi; Hanif Khan; Deepshikha (Indian Phytopathology, 2019)

Nanoencapsulated methyl salicylate as a biorational alternative of synthetic antifungal and aflatoxin B1 suppressive agents - Anupam Kujur; Amrita Yadav; Akshay Kumar; Prem Pratap Singh; Bhanu Prakash (Environmental Science and Pollution Research, 2019)

Stage-specific reprogramming of defense responsive genes during Lr24-mediated leaf rust resistance in wheat - Pramod Prasad; Siddanna Savadi; Subhash Chander Bhardwaj; Prem Lal Kashyap; Om Prakash Gangwar; Hanif Khan; Subodh Kumar; Ravinder Kumar; Virupaksh Patil (Journal of Plant Pathology, 2019)

Comparative Immunological and Biochemical Properties of the Epidermal Mucus from Three Brackishwater Fishes - Prem Kumar; T. Rajeshwaran; P. Priya; M. Kailasam; G. Biswas; T. K. Ghoshal; K. K. Vijayan; A. R. T. Arasu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Foliar application of organic and inorganic iron formulation induces differential detoxification response to improve growth and biofortification in soybean - Sandeep Sharma; Hina Malhotra; Priyanka Borah; Mukesh Kumar Meena; Prem Bindraban; Subhash Chandra; Veena Pande; Renu Pandey (Plant Physiology Reports, 2019)

Isolation and characterization of halotolerant bacilli from chickpea (Cicer arietinum L.) rhizosphere for plant growth promotion and biocontrol traits - Anjney Sharma; Prem Lal Kashyap; Alok Kumar Srivastava; Y. K. Bansal; Rajeev Kaushik (European Journal of Plant Pathology, 2019)

Genome-Wide Analysis of Microsatellites in Alternaria arborescens and Elucidation of the Function of Polyketide Synthase (PksJ) - Prassan Choudhary; Prem Lal Kashyap; Sanjay Kumar Goswami; Hillol Chakdar; Alok Kumar Srivastava; Anil Kumar Saxena (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Quantification and Characterization of Mannan Oligosaccharide Producing Yeasts isolated from Various Food Products - Shobha Gupta; Zarine P. Bhathena; Sarvendra Kumar; Prem Prakash Srivastava; Sanjay Balkrishna Jadhao (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Temporal Transcriptional Changes in SAR and Sugar Transport-Related Genes During Wheat and Leaf Rust Pathogen Interactions - Siddanna Savadi; Pramod Prasad; S. C. Bhardwaj; Prem Lal Kashyap; O. P. Gangwar; Hanif Khan; Subodh Kumar (Journal of Plant Growth Regulation, 2018)

Monitoring and Mapping Invasive Aquatic Weed Salvinia molesta using Multispectral Remote Sensing Technique in Tumaria Wetland of Uttarakhand, India - Nandkishor A. Ingole; A. S. Nain; Prem Kumar; Ramesh Chalal (Journal of the Indian Society of Remote Sensing, 2018)

Modeling of Electric Demand for Sustainable Energy and Management in India Using Spatio-Temporal DMSP-OLS Night-Time Data - Bismay Ranjan Tripathy; Haroon Sajjad; Christopher D. Elvidge; Yu Ting; Prem Chandra Pandey; Meenu Rani; Pavan Kumar (Environmental Management, 2018)

Protein requirement of juvenile striped catfish, Pangasianodon hypophthalmus - Manish Jayant; Ande Penchala Muralidhar; Narrottam Prasad Sahu; Kamal Kant Jain; Asim Kumar Pal; Prem Prakash Srivastava (Aquaculture International, 2018)

Enhancing the Solubility of Fenofibrate by Nanocrystal Formation and Encapsulation - Raj Kumar; Prem Felix Siril (AAPS PharmSciTech, 2018)

Trichoderma for climate resilient agriculture - Prem Lal Kashyap; Pallavi Rai; Alok Kumar Srivastava; Sudheer Kumar (World Journal of Microbiology and Biotechnology, 2017)

Population genetic structure of Rhizoctonia solani AG1IA from rice field in North India - Sanjay Kumar Goswami; Vineeta Singh; Prem Lal Kashyap (Phytoparasitica, 2017)

Aortic Regurgitation Generates a Kinematic Obstruction Which Hinders Left Ventricular Filling - Ikechukwu Okafor; Vrishank Raghav; Jose F. Condado; Prem A. Midha; Gautam Kumar; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2017)

Fate of Metals in Relation to Water and Sediment Properties in a Subtropical Lake in Central Himalaya, India - Shaikhom Inaotombi; Prem Kumar Gupta (Archives of Environmental Contamination and Toxicology, 2017)

Nanodiagnostics for plant pathogens - Prem Lal Kashyap; Sudheer Kumar; Alok K. Srivastava (Environmental Chemistry Letters, 2017)

A potato model intercomparison across varying climates and productivity levels - David H. Fleisher; Bruno Condori; Roberto Quiroz; Ashok Alva; Senthold Asseng; Carolina Barreda; Marco Bindi; Kenneth J. Boote; Roberto Ferrise; Angelinus C. Franke; Panamanna M. Govindakrishnan; Dieudonne Harahagazwe; et al. (Global Change Biology, 2017)
A potato crop multimodel assessment was conducted to quantify variation among models and evaluate responses to climate change. Nine modeling groups simulated agronomic and climatic responses at low‐input (Chinoli, Bolivia and Gisozi, Burundi)‐ and high‐input (Jyndevad, Denmark and Washington, United States) management sites. Two calibration stages were explored, partial (P1), where experimental dry matter data were not provided, and full (P2). The median model ensemble response outperformed any single model in terms of replicating observed yield across all locations. Uncertainty in simulated yield decreased from 38% to 20% between P1 and P2. Model uncertainty increased with interannual variability, and predictions for all agronomic variables were significantly different from one model to another ( P ET ), nitrogen uptake, and water use efficiency as compared to dry matter. A minimum of five partial, or three full, calibrated models was required for an ensemble approach to keep variability below that of common field variation. Model variation was not influenced by change in carbon dioxide (C), but increased as much as 41% and 23% for yield and ET , respectively, as temperature (T) or rainfall (W) moved away from historical levels. Increases in T accounted for the highest amount of uncertainty, suggesting that methods and parameters for T sensitivity represent a considerable unknown among models. Using median model ensemble values, yield increased on average 6% per 100‐ppm C, declined 4.6% per °C, and declined 2% for every 10% decrease in rainfall (for nonirrigated sites). Differences in predictions due to model representation of light utilization were significant ( P

Non‐annular response of sea ice cover in the Indian sector of the Antarctic during extreme SAM events - Pranab Deb; Mihir Kumar Dash; Subhra Prakash Dey; Prem Chand Pandey (International Journal of Climatology, 2017)
This study investigates the impact of wind‐induced sea ice drift on sea ice cover over the Indian Ocean sector of the Southern Ocean ( IOS ) in the contrasting Southern Annular Mode ( SAM ) years during a summer (February) and a winter (July) month. Analysis of reanalysis wind shows that during positive SAM events, westerlies show stronger and more zonal flow over the west IOS (west of 45°E), while a stronger northerly component is seen over the east IOS , to the south of 55°S during both February and July. This is attributed to the zonally asymmetric feature of sea level pressure over the IOS . A coupled ocean–sea ice model was forced with dynamical wind forcing for positive and negative SAM events during above months. The zonal contrast as seen in wind and surface current is transferred to the sea ice drift. A stronger zonal eastward sea ice drift is apparent over the west IOS , suggesting increased transport of sea ice from the Weddell Sea region in July. The eastward advection of sea ice results in piling of sea ice over west IOS and causes an increase in sea ice concentration and thickness. Over east IOS , the sea ice drift shows a strong southeastward anomaly from the sea ice edge towards the coast. This results in a piling of sea ice near the coast and a divergence of sea ice near the edge. This results in a negative anomaly in sea ice concentration and sea ice thickness over east IOS . Thus, the dynamical SAM forcing leads to a non‐annular response in sea ice cover over the IOS .

Cardamonin represses proliferation, invasion, and causes apoptosis through the modulation of signal transducer and activator of transcription 3 pathway in prostate cancer - Jingwen Zhang; Sakshi Sikka; Kodappully S. Siveen; Jong Hyun Lee; Jae-Young Um; Alan Prem Kumar; Arunachalam Chinnathambi; Sulaiman Ali Alharbi; Basappa; Kanchugarakoppal S. Rangappa; Gautam Sethi; Kwang Seok Ahn (Apoptosis, 2017)

Influence of Three Citrus Herbicides on Potential Production of Sorghum bicolor ‘Topper 76-6’ as a Bioenergy Crop - Patrick C. Wilson; Barrett Gruber; Youjian Lin; Prem Kumar; David Niebch; Sandra Wilson (Bulletin of Environmental Contamination and Toxicology, 2016)

Combined Effect of Heat Shock and Chlorine Fails to Elicit Acquired Thermal Tolerance in Labeo rohita Spawns - Jolyn Fernandes; A. K. Pal; Prem Kumar; P. P. Chandrachoodan; M. S. Akhtar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Silver nitrate promotes high-frequency multiple shoot regeneration in cotton (Gossypium hirsutum L.) by inhibiting ethylene production and phenolic secretion - G. Prem Kumar; S. Sivakumar; G. Siva; M. Vigneswaran; T. Senthil Kumar; N. Jayabalan (In Vitro Cellular & Developmental Biology - Plant, 2016)

Sustained Shoot Multiplication and Method for Overcoming In Vitro Browning in Medicinally Important Plant, Piper chaba Hunt - Dolly Rani; Prem Kumar Dantu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Comparative analysis of microsatellites in five different antagonistic Trichoderma species for diversity assessment - Shalini Rai; Prem Lal Kashyap; Sudheer Kumar; Alok Kumar Srivastava; Pramod W. Ramteke (World Journal of Microbiology and Biotechnology, 2016)

Moderate inhibition of mitochondrial function augments carotid body hypoxic sensitivity - Andrew P. Holmes; Philip J. Turner; Keith J. Buckler; Prem Kumar (Pflügers Archiv - European Journal of Physiology, 2016)

Optimization of sootblowing frequency to improve boiler performance and reduce combustion pollution - Lalatendu Pattanayak; Sai Prem Kumar Ayyagari; J. N. Sahu (Clean Technologies and Environmental Policy, 2015)

Biochemical and Physiological Stress Responses to Heat Shock and Their Recovery in Labeo rohita Fingerlings - Prem Kumar; Asim K. Pal; Narottam P. Sahu; Ashish K. Jha; Priyadarshani Priya (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

NF-κB in cancer therapy - Feng Li; Jingwen Zhang; Frank Arfuso; Arunachalam Chinnathambi; M. E. Zayed; Sulaiman Ali Alharbi; Alan Prem Kumar; Kwang Seok Ahn; Gautam Sethi (Archives of Toxicology, 2015)

Phytodiversity on fly ash deposits: evaluation of naturally colonized species for sustainable phytorestoration - Vimal Chandra Pandey; Prem Prakash; Omesh Bajpai; Akhilesh Kumar; Nandita Singh (Environmental Science and Pollution Research, 2015)

Stress mitigating and growth enhancing effect of dietary tryptophan in rohu (Labeo rohita, Hamilton, 1822) fingerlings - Prem Kumar; Shailesh Saurabh; A. K. Pal; N. P. Sahu; A. R. T. Arasu (Fish Physiology and Biochemistry, 2014)

Molecular Cloning and Characterization of the Gene Encoding Heat Shock Protein 70 from the Chicken (Gallus gallus) - Elza Neelima Mathew; Gurvinder Singh Brah; B. V. Sunil Kumar; Chandra Sekhar Mukhopadhyay; Prem Prakash Dubey (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Degradation of Sulphonated Azo Dye Red HE7B by Bacillus sp. and Elucidation of Degradative Pathways - Jyoti Kumar Thakur; Sangeeta Paul; Prem Dureja; K. Annapurna; Jasdeep C. Padaria; Madhuban Gopal (Current Microbiology, 2014)

DFT-based prediction of antifungal and insecticidal activities of perfluorophenyl antimony(III) and antimony(V) chlorides - Kiran Singhal; Vishnu Kumar Sahu; Pratibha Singh; Prem Raj (Medicinal Chemistry Research, 2014)

Suppression of essential pro-inflammatory signaling pathways by natural agents for the therapy of Multiple Myeloma - Sakshi Sikka; Muthu K. Shanmugam; Radhamani Kannaiyan; Rohit Surana; Eun Myoung Shin; Alan Prem Kumar; Gautam Sethi; Kwang Seok Ahn (Phytochemistry Reviews, 2014)

Simvastatin sensitizes human gastric cancer xenograft in nude mice to capecitabine by suppressing nuclear factor-kappa B-regulated gene products - Kanjoormana A. Manu; Muthu K. Shanmugam; Feng Li; Luxi Chen; Kodappully Sivaraman Siveen; Kwang Seok Ahn; Alan Prem Kumar; Gautam Sethi (Journal of Molecular Medicine, 2014)

Identification and characterization of ethanol utilizing fungal flora of oil refinery contaminated soil - Alok Kumar Srivastava; Pratiksha Singh; Rajesh Kumar Singh; Prem Lal Kashyap; Hillol Chakdar; Sudheer Kumar; Arun Kumar Sharma (World Journal of Microbiology and Biotechnology, 2014)

Cross-species transferability of microsatellite markers from Fusarium oxysporum for the assessment of genetic diversity in Fusarium udum - Sudheer Kumar; Shalini Rai; Deepak Kumar Maurya; Prem Lal Kashyap; Alok K. Srivastava; M. Anandaraj (Phytoparasitica, 2013)

Prevalence and risk factors associated with Cryptosporidium spp. infection in young domestic livestock in India - Prem Sagar Maurya; Radhamma Lakshmipathy Rakesh; Balaraju Pradeep; Saroj Kumar; Krishnendu Kundu; Rajat Garg; Hira Ram; Ashok Kumar; Partha Sarathi Banerjee (Tropical Animal Health and Production, 2013)

Isolation and characterization of gut bacteria of fruit fly, Bactrocera tau (Walker) - Chandra S. Prabhakar; Pankaj Sood; Sarbjit S. Kanwar; Prem N. Sharma; Ajay Kumar; Pawan K. Mehta (Phytoparasitica, 2013)

Comparison of Different Approaches to Establish a Core Collection of Andigena (Solanum tuberosum Group Andigena) Potatoes - J. Gopal; Vinod Kumar; Raj Kumar; Prem Mathur (Potato Research, 2013)

Myconanotechnology in agriculture: a perspective - Prem Lal Kashyap; Sudheer Kumar; Alok Kumar Srivastava; Arun Kumar Sharma (World Journal of Microbiology and Biotechnology, 2013)

The impact of acute and chronic catecholamines on respiratory responses to hypoxic stress in the rat - David Hauton; Andrew Holmes; Oliver Ziff; Prem Kumar (Pflügers Archiv - European Journal of Physiology, 2013)

Unusual circulation pattern during Indian summer monsoon failure in July 2002 and June 2009 - Dhrubajyoti Samanta; Mihir Kumar Dash; Prem Chand Pandey (Natural Hazards, 2013)

The study of microclimate in response to different plant community association in tropical moist deciduous forest from northern India - Soumit K. Behera; Ashish K. Mishra; Nayan Sahu; Amrit Kumar; Niraj Singh; Anoop Kumar; Omesh Bajpai; L. B. Chaudhary; Prem B. Khare; Rakesh Tuli (Biodiversity and Conservation, 2012)

Direct shoot regeneration from nodal, internodal and petiolar segments of Piper longum L. and in vitro conservation of indexed plantlets - Dolly Rani; Prem Kumar Dantu (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Lead Levels in Breast Milk, Blood Plasma and Intelligence Quotient: A Health Hazard for Women and Infants - C. Prince Jebadass Isaac; A. Sivakumar; C. Rebecca Prem Kumar (Bulletin of Environmental Contamination and Toxicology, 2012)

Plant defense activation and management of tomato root rot by a chitin-fortified Trichoderma/Hypocrea formulation - Manoj Kumar Solanki; Nidhi Singh; Rajesh Kumar Singh; Pratiksha Singh; Alok K. Srivastava; Sudheer Kumar; Prem L. Kashyap; Dilip K. Arora (Phytoparasitica, 2011)

Celastrol inhibits tumor cell proliferation and promotes apoptosis through the activation of c-Jun N-terminal kinase and suppression of PI3 K/Akt signaling pathways - Radhamani Kannaiyan; Kanjoormana Aryan Manu; Luxi Chen; Feng Li; Peramaiyan Rajendran; Aruljothi Subramaniam; Paula Lam; Alan Prem Kumar; Gautam Sethi (Apoptosis, 2011)

Ursolic acid inhibits multiple cell survival pathways leading to suppression of growth of prostate cancer xenograft in nude mice - Muthu K. Shanmugam; Peramaiyan Rajendran; Feng Li; Tarang Nema; Shireen Vali; Taher Abbasi; Shweta Kapoor; Ashish Sharma; Alan Prem Kumar; Paul C. Ho; Kam M. Hui; Gautam Sethi (Journal of Molecular Medicine, 2011)

A time course study on prothrombotic parameters and their modulation by anti-platelet drugs in hyperlipidemic hamsters - Vishal Singh; Manish Jain; Prem Prakash; Ankita Misra; Vivek Khanna; Rajiv Lochan Tiwari; Ravi Shankar Keshari; Shivendra Singh; Madhu Dikshit; Manoj Kumar Barthwal (Journal of Physiology and Biochemistry, 2011)

Erratum to: A Combination of Melatonin and Alpha Lipoic Acid has Greater Cardioprotective Effect than Either of them Singly Against Cadmium-Induced Oxidative Damage - Raktim Mukherjee; Sudeep Banerjee; Niraj Joshi; Prem Kumar Singh; Darshee Baxi; A. V. Ramachandran (Cardiovascular Toxicology, 2011)

A Combination of Melatonin and Alpha Lipoic Acid has Greater Cardioprotective Effect than Either of them Singly Against Cadmium-Induced Oxidative Damage - Raktim Mukherjee; Sudeep Banerjee; Niraj Joshi; Prem Kumar Singh; Darshee Baxi; A. V. Ramachandran (Cardiovascular Toxicology, 2011)

Persistence of Azoxystrobin in/on Grapes and Soil in Different Grapes Growing Areas of India - Vijay Tularam Gajbhiye; Suman Gupta; Irani Mukherjee; Shashi Bala Singh; Neera Singh; Prem Dureja; Yogesh Kumar (Bulletin of Environmental Contamination and Toxicology, 2011)

Performance of somaclones developed from intergeneric hybrids of sugarcane - S. Rajeswari; M. Krishnamurthi; Shinisekar; S. Prem Anand; S. Thirugnana Kumar (Sugar Tech, 2009)

Genetic Diversity in Metapenaeus dobsoni using RAPD Analysis - Prem Sagar Mishra; Aparna Chaudhari; Gopal Krishna; Dilip Kumar; W. S. Lakra (Biochemical Genetics, 2009)

Anti-dyslipidemic and antioxidant activities of different fractions of Pongamia pinnata (lin.) fruits - Gitika Bhatia; Anju Puri; Rakesh Maurya; Prem PrakashYadav; Mohammad Mubin Khan; Ashok Kumar Khanna; Jitender Kumar Saxena (Medicinal Chemistry Research, 2008)

Sex determination in 6 bovid species by duplex PCR - Prashant; Digpal S. Gour; Prem P. Dubey; Anubhav Jain; Subhash C. Gupta; Balwinder K. Joshi; Dinesh Kumar (Journal of Applied Genetics, 2008)

Anti-dyslipidemic and antioxidant activities of different fractions of Pongamia pinnata (lin.) fruits - Gitika Bhatia; Anju Puri; Rakesh Maurya; Prem PrakashYadav; Mohammad Mobin Khan; Ashok Kumar Khanna; Jitender Kumar Saxena (Medicinal Chemistry Research, 2008)

Root anatomy of Pinus taeda L.: seasonal and environmental effects on development in seedlings - Prem Kumar; Stephen W. Hallgren; Daryl E. Enstone; Carol A. Peterson (Trees, 2007)

Radioprotective properties of apple polyphenols: An in vitro study - Pankaj Chaudhary; Sandeep Kumar Shukla; I. Prem Kumar; I. Namita; Farhat Afrin; Rakesh Kumar Sharma (Molecular and Cellular Biochemistry, 2006)

Protein fingerprinting profiles in different strains of Aeromonas hydrophila isolated from diseased freshwater fish - Basanta Kumar Das; Surya Kanta Samal; Biswa Ranjan Samantaray; Prem Kumar Meher (World Journal of Microbiology and Biotechnology, 2005)

Induction of DNA-protein cross-links by Hippophae rhamnoides: Implications in radioprotection and cytotoxicity - H.C. Goel; I. Prem Kumar; Namita Samanta; S.V.S. Rana (Molecular and Cellular Biochemistry, 2003)

Modulation of chromatin organization by RH-3, a preparation of Hippophae rhamnoides, a possible role in radioprotection - I. Prem Kumar; Samanta Namita; H.C. Goel (Molecular and Cellular Biochemistry, 2002)

Structure and function of traditional agroforestry systems in the western Himalaya. II. Nutrient cycling - Om Parkash Toky; Pradeep Kumar; Prem Kumar Khosla (Agroforestry Systems, 1989)

Structure and function of traditional agroforestry systems in the western Himalaya. I. Biomass and productivity - Om Parkash Toky; Pradeep Kumar; Prem Kumar Khosla (Agroforestry Systems, 1989)

Relative induction of molecular forms of cytochrome P-450 in ?-hexachlorocyclohexane exposed rat liver microsomes - Ashwani Kumar; Prem Prakash Dwivedi (Archives of Toxicology, 1988)